Protein and biopolymer complexes and methods of making and using same

By preparing the complex of lactoferrin, anionic biopolymer and cationic biopolymer, the problem of lactoferrin is solved to heat treatment, and its structural stability and anti-bacterial activity are improved after heat treatment.

CN119604296APending Publication Date: 2025-03-11DAIRY MANAGEMENT INC +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380048061.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-16
Filing Date
2023-05-16
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Lactoferrin is sensitive to heat treatment-induced degeneration, especially under neutral pH conditions, resulting in structural changes and loss of biological function.

Method used

By preparing a complex containing lactoferrin, anionic biopolymer and cationic biopolymer, electrostatic interactions are used to bind them under pH conditions in the range of about 3 to 5 to form a stable ternary complex.

Benefits of technology

This method significantly improves the thermal stability and antibacterial activity of lactoferrin, ensuring that it can retain biological functions after heat treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604296A_ABST
    Figure CN119604296A_ABST
Patent Text Reader

Abstract

Described herein are complexes comprising proteins, anionic biopolymers, and cationic biopolymers, as well as methods of making and using such complexes. The complex may include lactoferrin, gelatin, and polysaccharide.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Statement on Electronic Submission of Sequence Listings

[0002] A sequence listing in XML text format generated on April 25, 2023 and submitted herewith, entitled 1213-3WO_ST26.xml, 7,184 bytes in size, is hereby incorporated by reference into the specification for disclosure.

[0003] field

[0004] The present invention relates to complexes comprising proteins, anionic biopolymers and cationic biopolymers and methods of making and using such complexes.

[0005] background

[0006] Lactoferrin (LF) is an iron-binding multifunctional protein found in many biological secretions, including milk. It has iron-binding / transferring, antibacterial, antiviral, anti-inflammatory and anti-carcinogenic properties. It promotes cell growth and detoxifies harmful free radicals, and has antibacterial, antiviral, anti-inflammatory and anti-carcinogenic properties. Due to the multiple biological functions of LF, it has been incorporated into many commercial products, including infant formula, nutritional supplements, therapeutic drinks and cosmetics. However, LF is sensitive to denaturation induced by heat treatment, especially under neutral pH conditions, which can cause structural changes and loss of biological function. SUMMARY OF THE INVENTION

[0008] A first aspect of the present invention relates to a complex comprising: a protein; an anionic biopolymer; and a cationic biopolymer; wherein the protein, the anionic biopolymer and the cationic biopolymer are bound by electrostatic interactions.

[0009] A second aspect of the present invention relates to a composition comprising the complex of the present invention. In certain embodiments, the composition is an aqueous composition.

[0010] Another aspect of the invention relates to a method of preparing a complex, the method comprising: providing a composition comprising a protein, an anionic biopolymer, and a cationic biopolymer at a pH in the range of about 3, 3.5 or 4 to about 4.5 or 5; and mixing the composition to provide the complex.

[0011] Another aspect of the present invention relates to an article comprising a complex of the present invention and / or a composition of the present invention. In certain embodiments, the article is a food product (eg, infant formula, dairy product, etc.), a nutritional supplement, a therapeutic drink and / or a cosmetic.

[0012] It should be noted that aspects of the invention described with respect to one embodiment may be incorporated in different embodiments, although there is no relevant special description. That is, all embodiments and / or features of any embodiment may be combined in any manner and / or combination. The applicant reserves the right to change any originally submitted claims and / or submit any new claims accordingly, including the right to amend any originally submitted claims to rely on and / or incorporate any features of any other one or more claims, although protection was not initially claimed in this manner. These and other objects and / or aspects of the invention are explained in detail in the specification described below. By reading the subsequent drawings and detailed description of the preferred embodiments, those of ordinary skill in the art will understand the further features, advantages and details of the invention, and such description is merely an illustration of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 Shown are diagrams depicting the use of branched polysaccharides ( Figure 1 , panel a) or linear polysaccharides ( Figure 1 , Panel b) Schematic diagram of an exemplary method for preparing the ternary complex of the present invention.

[0015] Figure 2 A graph showing the turbidity variation as a function of mass ratio composition of a mixture comprising lactoferrin (LF), gelatin (G) and a polysaccharide (PS) selected from gum arabic (GA), soy soluble polysaccharide (SSP), high methyl pectin (HMP), Kappa carrageenan (Kappa) and Iota carrageenan (Iota), with a total concentration of 0.2% at pH 4.

[0016] Figure 3 A graph showing the turbidity of a PS(GA / SSP)-LF-G mixture as a function of the mass ratio composition, with a total concentration of 1%, at pH 4 is shown.

[0017] Figure 4 A plot showing the zeta potential of a PS(GA / SSP / HMP / Kappa / Iota)-LF-G mixture as a function of mass ratio composition, with a total concentration of 1%, at pH 4.

[0018] Figure 5 A graph showing the turbidity of the PS(GA / SSP / HMP / Kappa / Iota)-LF-G mixture at pH 4 as a function of salt concentration (0-500 mM) is shown.

[0019] Figure 6 Optical microscopy images of PS(GA / SSP / HMP / Kappa / Iota)-LF-G mixtures are shown.

[0020] Figure 7 Confocal microscopy images of PS(GA / HMP / Iota)-LF-G mixtures are shown, in which LF was labeled with FTIC (light grey).

[0021] Figure 8 Turbidimetric graphs of unheated and heated (75°C / 2 min or 90°C / 2 min) LF and the redispersed ternary complex in PBS (10 mM, pH 7) are shown.

[0022] Fig. 9 Shown are graphs of the average particle size of unheated and heated (75°C / 2 min or 90°C / 2 min) LF and the redispersed ternary complex in PBS (10 mM, pH 7).

[0023] Fig.10 Shown are SDS-PAGE gel images of unheated and heated (75°C / 2 min or 90°C / 2 min) LF and the redispersed ternary complex in PBS (10 mM, pH 7).

[0024] Fig.11 Another SDS-PAGE gel image of unheated and heated (75°C / 2 min or 90°C / 2 min) LF and the redispersed ternary complex in PBS (10 mM, pH 7) is shown.

[0025] Fig.12 Circular dichroism spectra of unheated and heated (75°C / 2 min or 90°C / 2 min) LF and the redispersed ternary complex in PBS (10 mM, pH 7) are shown.

[0026] Fig.13 Intrinsic fluorescence images of unheated and heated (75°C / 2 min) LF and redispersed ternary complex in PBS (10 mM, pH 7) are shown.

[0027] Fig.14 Shown are graphs of peak fluorescence changes of unheated and heated (75°C / 2 min) LF and redispersed ternary complex in PBS (10 mM, pH 7).

[0028] Fig.15 Shown is the growth of Staphylococcus aureus expressed as OD625, which was incubated with a range of concentrations (w / v%) of LF at 37°C for 0 h, 24 h or 48 h ( Fig.15 A), and incubated at 37°C with LF (0.1 w / v%) and the redispersed ternary complex (0.2 w / v%) in PBS (10 mM, pH 7), respectively, before heat treatment ( Fig.15 Panel B), after heat treatment at 75℃ / 2 minutes ( Fig.15 C), and after heat treatment at 90℃ / 2 minutes ( Fig.15 Pairwise comparisons between each sample and the control were performed, and the significant difference levels were shown as *(p≤0.05), **(p≤0.01), ***(p≤0.001), or ****(p≤0.0001).

[0029] Fig.16 Shown is the growth of Escherichia coli expressed as OD625, which was incubated with a range of concentrations (w / v%) of LF at 37°C for 0 h, 12 h or 24 h ( Fig.16 A), and incubated at 37°C with LF (0.1 w / v%) and the redispersed ternary complex (0.2 w / v%) in PBS (10 mM, pH 7), respectively, before heat treatment ( Fig.16 Panel B), after heat treatment at 75℃ / 2 minutes ( Fig.16 C), and after heat treatment at 90℃ / 2 minutes ( Fig.16 Pairwise comparisons between each sample and the control were performed, and the significant difference levels were shown as *(p≤0.05), **(p≤0.01), ***(p≤0.001), or ****(p≤0.0001).

[0030] Fig.17 The PS(GA / SSP / HMP / Kappa / Iota)-LF-G complex was shown to be Fig.17 Panels A1-E1) and 200nm( Fig.17 Scanning electron microscopy images at the scale of (panels A2-B2).

[0031] Fig.18 The turbidity of LF (0.1 w / v%) and the redispersed ternary complex (0.2 w / v%) in PBS (10 mM, pH 7) after oil bath heating (145 °C) for 0 s, 2 s, 10 s, 30 s and 60 s is shown. Fig.18 Panel A) and average particle size ( Fig.18 Figure 2 (inset B).

[0032] Detailed Description

[0033] The present invention will now be described hereinafter with reference to the accompanying drawings and Examples, in which embodiments of the present invention are shown. This description is not intended to be an inventory of all different ways in which the present invention can be implemented or an inventory of all features that can be added to the present invention. For example, features explained about an embodiment can be incorporated into other embodiments, and features explained about a specific embodiment can be deleted from the embodiment. Therefore, the present invention contemplates that, in certain embodiments of the present invention, any feature or feature combination described herein can be excluded or omitted. In addition, many modifications and additions to the various embodiments proposed herein will be apparent to those skilled in the art based on the disclosure of the present invention, and it will not depart from the present invention. Therefore, the following description is intended to explain certain specific embodiments of the present invention, rather than to describe in detail all its arrangements, combinations and variations.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. The terminology used in the description of the invention herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0035] All publications, patent applications, patents, and other references cited herein are incorporated by reference in their entirety for the teachings relevant to the sentence and / or paragraph in which the reference appears.

[0036] Unless the context indicates otherwise, it is specifically intended that the various features of the invention described herein may be used in any combination. In addition, the present invention also contemplates that any feature or combination of features described herein may be excluded or omitted in certain embodiments of the present invention. For illustration, if the specification states that a composition comprises components A, B, and C, it is specifically intended that any one or combination of A, B, or C may be omitted and abandoned, either individually or in any combination.

[0037] As used in the description of the invention and the appended claims, the singular forms "a", "an" and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.

[0038] Furthermore, "and / or" as used herein means and encompasses any and all possible combinations of one or more of the associated listed items, as well as the lack of a combination when interpreted in the alternative ("or").

[0039] As used herein, the term "about" when referring to a measurable value (such as an amount or concentration, etc.) is intended to encompass variations of ±10%, ±5%, ±1%, ±0.5%, or even ±0.1% of the specified value as well as the specified value. For example, "about X," where X is a measurable value, is intended to include X as well as variations of ±10%, ±5%, ±1%, ±0.5%, or even ±0.1% of X. The ranges of measurable values ​​provided herein may include any other ranges and / or single values ​​therein.

[0040] Phrases such as "between X and Y" and "between about X and Y" used herein should be interpreted to include X and Y. Phrases such as "between about X and Y" used herein mean "between about X and about Y" and phrases such as "from about X to Y" mean "from about X to about Y."

[0041] Recitation of ranges of values ​​herein are merely intended to serve as a shorthand method of referring individually to each separate value falling within the range, unless otherwise indicated herein, and each separate value is incorporated into the specification as if it were individually set forth herein. For example, if a range of 10 to 15 is disclosed, then 11, 12, 13, and 14 are also disclosed.

[0042] As used herein, the terms “comprise” and “include” specify the presence of stated features, integers, steps, operations, elements and / or components, but do not preclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or groups thereof.

[0043] The transition phrase "consisting essentially of" as used herein means that the scope of a claim should be interpreted to encompass the specific materials or steps recited in the claim and those that do not materially affect the basic and novel characteristics of the claimed invention. Therefore, the term "consisting essentially of" when used in the claims of the present invention should not be interpreted as being equivalent to "comprising...".

[0044] As used herein, the terms "increase," "increase," "enhance," "improve," and "improve" (and grammatical variations thereof) describe an increase of at least about 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 100%, 150%, 200%, 300%, 400%, 500% or more, such as compared to another measurable property or quantity (e.g., a control value).

[0045] As used herein, the terms "reduce," "decrease," and "lower" (and grammatical variations thereof) describe, for example, a reduction of at least about 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, 97%, 98%, 99%, or 100%, such as compared to another measurable property or quantity (e.g., a control value). In certain embodiments, such reduction can result in no or substantially no (i.e., a negligible amount, e.g., less than about 10% or even 5%) detectable activity or amount.

[0046] A "part" or "fragment" (including domains) of a nucleotide sequence or polypeptide will be understood to refer to a nucleotide sequence or polypeptide that is shortened in length relative to a reference nucleotide sequence or polypeptide (e.g., shortened by 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or more residues (e.g., nucleotides or peptides) respectively), and comprises a nucleotide sequence or polypeptide of consecutive residues, consisting essentially of %, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% identity) to the reference nucleotide sequence or polypeptide.

[0047] "Sequence identity" as used herein refers to the degree to which two optimally aligned polynucleotide or polypeptide sequences remain unchanged over a comparison window of components (e.g., nucleotides or amino acids). "Identity" can be easily calculated by known methods, including, but not limited to, those described in the following documents: Computational Molecular Biology (Lesk, AM, ed.) Oxford University Press, New York (1988); Biocomputing: Informatics and Genome Projects (Smith, DW, ed.) Academic Press, New York (1993); Computer Analysis of Sequence Data, Part I (Griffin, AM, and Griffin, HG, ed.) Humana Press, New Jersey (1994); Sequence Analysis in Molecular Biology (von Heinje, G., ed.) Academic Press (1987); and Sequence Analysis Primer (Gribskov, M. and Devereux, J., ed.) Stockton Press, New York (1991).

[0048] As used herein, the term "percent sequence identity" or "percent identity" refers to the percentage of identical nucleotides in a linear polynucleotide sequence between a reference ("query") polynucleotide molecule (or its complementary strand) and a test ("subject") polynucleotide molecule (or its complementary strand) when the two sequences are optimally aligned. In certain embodiments, "percent identity" may refer to the percentage of identical amino acids in an amino acid sequence compared to a reference polypeptide.

[0049] As used herein, the phrases "substantially identical" or "substantial identity" in the context of two nucleic acid molecules, nucleotide sequences, or protein sequences mean that two or more sequences or subsequences have at least about 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 99.5%, or 100% nucleotide or amino acid residue identity when compared and aligned for maximum correspondence as measured using one of the following sequence comparison algorithms or by visual inspection. In certain embodiments of the invention, the substantial identity is present in a continuous nucleotide region of a nucleotide sequence of the invention of about 10 nucleotides to about 20 nucleotides, about 10 nucleotides to about 25 nucleotides, about 10 nucleotides to about 30 nucleotides, about 15 nucleotides to about 25 nucleotides, about 30 nucleotides to about 40 nucleotides, about 50 nucleotides to about 60 nucleotides, about 70 nucleotides to about 80 nucleotides, about 90 nucleotides to about 100 nucleotides or more nucleotides in length and any range therebetween up to the full length of the sequence. In certain embodiments, the nucleotide sequence may be substantially identical in at least about 20 nucleotides (e.g., about 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40 nucleotides). In certain embodiments, substantially identical nucleotides or protein sequences perform substantially the same function as its substantially identical nucleotides (or encoded protein sequences).

[0050] For sequence comparison, usually one sequence serves as a reference sequence to which a test sequence is compared. When using a sequence comparison algorithm, the test sequence and the reference sequence are input into a computer, subsequence coordinates are specified if necessary, and sequence algorithm program parameters are specified. The sequence comparison algorithm then calculates the sequence identity percentage of the test sequence relative to the reference sequence based on the specified program parameters.

[0051] Optimal alignment of sequences for alignment windows is well known to those skilled in the art and can be performed by tools such as the local homology algorithm of Smith and Waterman, the homology alignment algorithm of Needleman and Wunsch, the search similarity method of Pearson and Lipman, and optionally computerized implementations of these algorithms such as those available as Wisconsin (Accelrys Inc., San Diego, CA) part obtained GAP, BESTFIT, FASTA and TFASTA.The " identity score " of the comparison section of test sequence and reference sequence is the number of identical components common to the sequences of two comparisons divided by the total number of components in the reference sequence section, for example, the smaller definition part of whole reference sequence or reference sequence.Sequence identity percentage is expressed as identity score multiplied by 100.The comparison of one or more polynucleotide sequences can be for full-length polynucleotide sequence or its part, or for longer polynucleotide sequence.For purposes of the present invention, BLASTX 2.0 version (for the nucleotide sequence of translation) and BLASTN 2.0 version (for polynucleotide sequence) can also be used to determine " identity percentage ".

[0052] According to embodiments of the present invention, complexes comprising proteins, anionic biopolymers, and cationic biopolymers are provided. The complexes of the present invention can be ternary complexes because the complexes comprise three different components, such as proteins, anionic biopolymers, and cationic biopolymers that are different from each other (e.g., different in chemical structure). In certain embodiments, the complexes of the present invention comprise at least three different components, such as proteins, anionic biopolymers, and cationic biopolymers that are different from each other (e.g., different in chemical structure).

[0053] The complexes of the invention may comprise one or more proteins, one or more anionic biopolymers and one or more cationic biopolymers, which may bind to each other via electrostatic interactions. The complexes of the invention may have a zeta potential of about -5, -4, -3, -2, -1 or 0 mV to about +1, +2, +3, +4 or +5 mV, optionally when present in a composition (e.g., water and / or buffer) having a pH of about 3, 3.5 or 4 to about 4.5, 5, 5.5, 6, 6.5, 7 or 7.5. In certain embodiments, the complexes of the invention have a zeta potential of about -5, -4, -3, -2, -1, 0, +1, +2, +3, +4 or +5 mV, optionally when present in a composition (e.g., water and / or buffer) having a pH of about 3, 3.5 or 4 to about 4.5, 5, 5.5, 6, 6.5, 7 or 7.5. In certain embodiments, the complexes of the invention have a zeta potential of about 0 mV, optionally when present in a composition (e.g., water and / or buffer) having a pH of about 3, 3.5 or 4 to about 4.5, 5, 5.5, 6, 6.5, 7 or 7.5. The complexes of the invention may have a net negative charge at a pH of about 6.5 to about 7.5, optionally at a pH of about 6.5, 7 or 7.5.

[0054] The complexes of the invention may comprise a protein, anionic biopolymer and / or cationic biopolymer in an amount of about 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or 85% w / w or more of the complex. In certain embodiments, the protein, anionic biopolymer and / or cationic biopolymer is present in the complexes of the invention in an amount of about 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or 85% w / w of the complex. In certain embodiments, the complexes of the invention comprise a protein in an amount of about 30%, 35%, or 40% to about 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, or 85% w / w, a cationic biopolymer in an amount of about 1%, 5%, or 10% to about 15%, 20%, 25%, 30%, 35%, or 40% w / w, and an anionic biopolymer in an amount of about 1%, 5%, or 10% to about 15%, 20%, 25%, 30%, 35%, or 40% w / w. In certain embodiments, the complexes comprise a protein in an amount of about 40% to about 75% w / w, a cationic biopolymer in an amount of about 10% to about 30% w / w, and an anionic biopolymer in an amount of about 10% to about 30% w / w.

[0055] One or more (e.g., 1, 2, 3, 4, 5, 10, 15, 20, 30, 40, or 50 or more) proteins may be present in the complexes of the invention. In certain embodiments, the complexes of the invention comprise two or more proteins that may be identical or different from one another. In certain embodiments, the complexes of the invention comprise one or more identical protein molecules (e.g., single proteins and / or protein monomers). The proteins present in the complexes of the invention and / or used to prepare the complexes of the invention may have a net positive charge, optionally at a pH of about 3, 3.5, or 4 to about 4.5, 5, 6, 7, or 8. In certain embodiments, the proteins present in and / or used to prepare the complexes of the invention can have a zeta potential of greater than about +10 mV, such as about +11, +12, +13, +14, +15, +16, +17, +18, +19, +20, +21, +22, +23, +24, +25, +26, +27, +28, +29, or +30 mV or more, optionally when present in a composition (e.g., water and / or a buffer) having a pH of about 3, 3.5, or 4 to about 4.5 or 5.

[0056] The protein present in the complex of the present invention and / or used to prepare the complex of the present invention may have a globular structure. In certain embodiments, the protein present in the complex of the present invention and / or used to prepare the complex of the present invention is soluble in water at a pH of less than about 8, such as about 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5 or 8, and optionally has a solubility of about 5, 10, 15 or 20 mg / L or more in water at a pH of less than about 8 and at about 25°C. In certain embodiments, the protein present in the complex of the present invention and / or used to prepare the complex of the present invention is a milk protein. As used herein, "milk protein" means a protein naturally present in dairy products and / or milk and / or a protein derived from such a naturally occurring protein, whose amino acid sequence has at least 70% sequence identity with the amino acid sequence of the naturally occurring protein. For example, in certain embodiments, the milk protein is naturally present in milk (e.g., animal milk) and / or the protein is isolated from milk, or the amino acid sequence of the protein prepared by synthesis has at least 70% sequence identity with the amino acid sequence of the naturally occurring protein.

[0057] Exemplary proteins that may be present in the complex of the present invention and / or used to prepare the complex of the present invention include, but are not limited to, lactoferrin, alpha lactalbumin, lysozyme and / or osteopontin. In certain embodiments, the complex of the present invention comprises lactoferrin. The protein of the present invention may be from any source (e.g., plants, animals, etc.). In certain embodiments, the protein is obtained and / or derived from an animal such as a mammal (e.g., cattle, goats, sheep or humans). In certain embodiments, the amino acid sequence of the protein present in the complex of the present invention has about 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or 100% sequence identity with one or more of SEQ ID NOs: 1-5. In certain embodiments, the amino acid sequence of a protein present in a complex of the invention has at least about 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or more sequence identity to one or more of SEQ ID NOs: 1-5. In certain embodiments, the amino acid sequence of a protein present in a complex of the invention has about 100% sequence identity to one or more of SEQ ID NOs: 1-5.

[0058] One or more (e.g., 1, 2, 3, 4, 5, 10, 15, 20, 30, 40, or 50 or more) cationic biopolymers can be present in the complexes of the invention. In certain embodiments, the complexes of the invention comprise two or more cationic biopolymers that can be the same or different from each other. In certain embodiments, the complexes of the invention comprise one or more identical cationic biopolymer molecules (e.g., a single biopolymer compound). The cationic biopolymers present in the complexes of the invention and / or used to prepare the complexes of the invention can have a net positive charge, optionally at a pH of about 3, 3.5, or 4 to about 4.5, 5, 6, 7, or 8. In certain embodiments, cationic biopolymers present in and / or used to prepare complexes of the invention can have a zeta potential greater than about +10 mV, such as about +11, +12, +13, +14, +15, +16, +17, +18, +19, +20, +21, +22, +23, +24, +25, +26, +27, +28, +29, or +30 mV or more, optionally when present in a composition (e.g., water and / or buffer) having a pH of about 3, 3.5, or 4 to about 4.5 or 5. Cationic biopolymers present in and / or used to prepare complexes of the invention can have a pi and / or pKa of about 7 or more, such as about 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11 or more.

[0059] As used herein, "cationic biopolymer" refers to a polymer that carries or can carry a positive charge and is produced by a living organism or is a derivative thereof and / or is prepared by synthesis to have a structure consistent with a polymer produced by a living organism or a derivative thereof. In certain embodiments, the cationic biopolymer has at least one free amine and / or hydroxyl group on most of the monomer units of the polymer. In certain embodiments, the free amine and / or hydroxyl groups may be present on each monomer unit of the polymer backbone. Exemplary cationic biopolymers include, but are not limited to, proteins, polyamino acids, and / or polysaccharides that can carry a positive charge (optionally having a net positive charge). It will be understood by a person of ordinary skill in the art that cationic biopolymers can be obtained by synthesis (e.g., by laboratory synthesis) and / or obtained and / or derived from nature (e.g., from a living or formerly living organism). Therefore, the cationic biopolymer may be the same as a polymer found in nature (i.e., a natural cationic biopolymer), or may be a derivative thereof. For example, the cationic biopolymer of the present invention may be a derivative of a polymer produced by a living organism, the derivative being produced by a synthetic method used to obtain or isolate the biopolymer from nature. In certain embodiments, the cationic biopolymer may be a polymer produced by bacteria and / or microorganisms. Exemplary cationic biopolymers that may be present in the complex of the present invention and / or used to prepare the complex of the present invention include, but are not limited to, gelatin, chitosan, lysozyme, and / or polyamino acids. In certain embodiments, the complex of the present invention comprises gelatin. The cationic biopolymer may be a biopolymer naturally found in animals, plants, and / or fungi, and / or may be derived from such naturally occurring biopolymers. In certain embodiments, the cationic biopolymer is a biopolymer naturally present in and isolated from animals, plants, and / or fungi. In certain embodiments, the cationic biopolymer is synthetically prepared based on biopolymers naturally found in animals, plants, and / or fungi. In certain embodiments, the cationic biopolymer is obtained from a source (e.g., animals, plants, and / or fungi) and / or is synthetically prepared based on natural biopolymers, and the obtained and / or prepared biopolymer is modified (e.g., modified to have cationic functional groups, etc.). The cationic biopolymer of the present invention may come from any source (e.g., plants, animals, etc.). In certain embodiments, the cationic biopolymer is obtained and / or derived from an animal such as a mammal (eg, cow, goat, sheep, or human).

[0060] One or more (e.g., 1, 2, 3, 4, 5, 10, 15, 20, 30, 40, or 50 or more) anionic biopolymers can be present in the complexes of the invention. In certain embodiments, the complexes of the invention comprise two or more anionic biopolymers that can be the same or different from each other. In certain embodiments, the complexes of the invention comprise one or more identical anionic biopolymer molecules (e.g., a single biopolymer compound). The anionic biopolymers present in the complexes of the invention and / or used to prepare the complexes of the invention can have a net negative charge, optionally at a pH of about 3, 3.5, or 4 to about 4.5, 5, 6, 7, or 8. In certain embodiments, anionic biopolymers present in and / or used to prepare complexes of the invention, optionally when present in a composition (e.g., water and / or a buffer) having a pH of about 3, 3.5, or 4 to about 4.5 or 5, can have a zeta potential of less than about -10 mV, such as about -11, -12, -13, -14, -15, -16, -17, -18, -19, -20, -21, -22, -23, -24, -25, -26, -27, -28, -29, -30, -31, -32, -33, -34, -35, -36, -37, -38, -39, -40, -41, -42, -43, -44, -45, -46, -47, -48, -49, -50, -51, -52 In some embodiments, the anionic biopolymers present in the complexes of the invention and / or used to prepare the complexes of the invention have a zeta potential in the range of about -10 mV to about -25 mV, optionally when present in a composition (e.g., water and / or buffer) having a pH of about 3, 3.5 or 4 to about 4.5 or 5. In certain embodiments, anionic biopolymers present in and / or used to prepare complexes of the invention have a zeta potential in the range of about -35 mV to about -55 mV, optionally when present in a composition (e.g., water and / or buffer) having a pH of about 3, 3.5, or 4 to about 4.5 or 5. Anionic biopolymers present in and / or used to prepare complexes of the invention can have a pKa of about 4 or less, such as about 4, 3.5, 3, 2.5, 2, 1.5, or 1 or less.

[0061] As used herein, "anionic biopolymer" refers to a polymer that carries or can carry a negative charge and is produced by a living organism or is a derivative thereof and / or is prepared by synthesis to have a structure consistent with a polymer produced by a living organism or a derivative thereof. In certain embodiments, anionic biopolymers have at least one free amine and / or hydroxyl group on most monomer units of the polymer. In certain embodiments, free amine and / or hydroxyl groups may be present on each monomer unit of the polymer backbone. Exemplary anionic biopolymers include, but are not limited to, proteins, polyamino acids, glycosaminoglycans, glycoproteins, and / or polysaccharides that can carry a negative charge (optionally having a net negative charge). It will be understood by those of ordinary skill in the art that anionic biopolymers can be obtained by synthesis (e.g., by laboratory synthesis) and / or obtained and / or derived from nature (e.g., from living or formerly living organisms). Therefore, anionic biopolymers can be the same as polymers found in nature (i.e., natural anionic biopolymers), or can be derivatives thereof. For example, the anionic biopolymer of the present invention may be a derivative of a polymer produced by a living organism, the derivative being produced by a synthetic method for obtaining or isolating the biopolymer from nature. In certain embodiments, the anionic biopolymer may be a polymer produced by bacteria and / or microorganisms. In certain embodiments, the anionic biopolymer present in the complex of the present invention and / or used to prepare the complex of the present invention is a polysaccharide, a glycosaminoglycan, a glycoprotein and / or a polyamino acid. In certain embodiments, the complex of the present invention comprises a polysaccharide. In certain embodiments, the complex of the present invention comprises a linear polysaccharide (i.e., a linear polysaccharide of monosaccharides linked / attached to a plant, optionally wherein each of the monosaccharides is linked by an α-1,4-glycosidic bond or a β-1,4-glycosidic bond). In certain embodiments, the complex of the present invention comprises a branched polysaccharide (e.g., a polysaccharide comprising two or more monosaccharides linked by an α-1,4-glycosidic bond and two or more monosaccharides linked by an α-1,6-glycosidic bond). The anionic biopolymer may be a biopolymer naturally found in animals, plants and / or fungi and / or may be derived from such a naturally occurring biopolymer. In certain embodiments, anionic biopolymers are biopolymers naturally present in and isolated from animals, plants and / or fungi. In certain embodiments, anionic biopolymers are synthetically prepared based on biopolymers naturally found in animals, plants and / or fungi. In certain embodiments, anionic biopolymers are obtained from a source (e.g., animals, plants and / or fungi) and / or synthetically prepared based on natural biopolymers, and the obtained and / or prepared biopolymers are modified (e.g., modified to have anionic functional groups, etc.). Anionic biopolymers of the present invention can come from any source (e.g., plants, animals, etc.).In certain embodiments, the anionic biopolymer is obtained and / or derived from an animal such as a mammal (eg, cow, goat, sheep, or human).

[0062] Other exemplary anionic biopolymers that may be present in the complexes of the present invention and / or used to prepare the complexes of the present invention include, but are not limited to, gum arabic, high methyl pectin (HMP) (e.g., HMP having a degree of esterification greater than about 50%), Kappa-carrageenan, Iota-carrageenan, dextran sulfate, sodium hyaluronate, acacia gum, xanthan gum, gellan gum, and / or plant soluble polysaccharides (e.g., soy soluble polysaccharides and / or lupin soluble polysaccharides). In certain embodiments, anionic biopolymers that may be present in the complexes of the present invention and / or used to prepare the complexes of the present invention include gum arabic, acacia gum, dextran sulfate, sodium hyaluronate, and / or plant soluble polysaccharides (e.g., soy soluble polysaccharides and / or lupin soluble polysaccharides). In certain embodiments, anionic biopolymers that may be present in the complexes of the invention and / or used to prepare the complexes of the invention include HMP (e.g., HMP having a degree of esterification greater than about 50%), Kappa-carrageenan, Iota-carrageenan, xanthan gum, and / or gellan gum. In certain embodiments, anionic biopolymers (e.g., polysaccharides) present in the complexes of the invention and / or used to prepare the complexes of the invention have a molecular weight (e.g., average molecular weight) in the range of about 50, 100, or 150 kDa to about 200, 250, or 300 kDa. In certain embodiments, anionic polymers have a molecular weight (e.g., average molecular weight) of about 50, 100, 150, 200, 250, or 300 kDa.

[0063] In certain embodiments, the proteins, cationic biopolymers, and / or anionic biopolymers present in the complexes of the invention and / or used to prepare the complexes of the invention are food grade components. As used herein, "food grade component" means a component (e.g., compound, ingredient, biopolymer, etc.) that is safe for consumption by an animal (e.g., a human) and / or is intended for ingestion by an animal (e.g., a human). In certain embodiments, the proteins, cationic biopolymers, and anionic biopolymers of the invention are each different food grade components present in the complexes of the invention. In certain embodiments, the proteins, cationic biopolymers, and anionic biopolymers in the complexes of the invention are each obtained and / or derived from natural products (e.g., foods, plants, animal byproducts (e.g., milk), etc.).

[0064] In certain embodiments, the complex of the present invention comprises lactoferrin, a polysaccharide (eg, a branched polysaccharide or a linear polysaccharide), and gelatin. In certain embodiments, the complex of the present invention comprises lactoferrin, gum arabic, and gelatin.

[0065] The complex of the present invention can be dried, optionally by freeze drying and / or spray drying a composition (e.g., an aqueous composition) comprising the complex. In certain embodiments, the dried complex comprises water in an amount of about 0% to about 5% (by weight) of the dried complex. In certain embodiments, the dried complex is free of water. In certain embodiments, the complex of the present invention is cross-linked, optionally using a cross-linking agent (such as, but not limited to, transglutaminase, glyceraldehyde, dialdehydic pectin and / or genipin).

[0066] In certain embodiments, the complex of the present invention is a complex aggregate in a liquid (e.g., water and / or a buffer such as phosphate buffered saline). "Complex aggregate" as used herein means a liquid droplet formed by associating liquid-liquid phase separation in a mixture of multivalent, oppositely charged molecules (e.g., oppositely charged biopolymers). The aggregate complex can be dried and / or hardened to form a solid phase. In certain embodiments, the complex of the present invention is a multiphase aggregate in a liquid because the complex aggregate has two or more (e.g., 2, 3, 4 or more) phases. In certain embodiments, the complex of the present invention is a multiphase aggregate in a liquid, and the complex has two phases (e.g., an inner phase and an outer phase). In certain embodiments, the complex of the present invention has an aggregate-in-aggregate structure in a liquid, and the complex comprises an inner aggregate and an outer aggregate. The inner aggregate can comprise a protein (e.g., lactoferrin) and an anionic biopolymer (e.g., a polysaccharide), and / or the outer aggregate can comprise an anionic biopolymer (e.g., a polysaccharide) and a cationic biopolymer (e.g., gelatin). In certain embodiments, the complex of the present invention is not a binary aggregate complex, and the binary aggregate complex is a complex aggregate formed by only two different molecules (e.g., two different biopolymers). In certain embodiments, the complex of the present invention is an interpolymer complex. "Interpolymer complex" as used herein means a coprecipitate or aggregate comprising a protein, a cationic biopolymer and an anionic biopolymer formed by electrostatic interactions. In certain embodiments, an anionic biopolymer and / or a cationic biopolymer is encapsulated in the protein of the complex of the present invention.

[0067] The complexes of the present invention can be particles. In certain embodiments, the complexes are nanoparticles. In certain embodiments, the complexes are microparticles. The complexes of the present invention can have a size (e.g., diameter) in at least one dimension of about 50, 75, 100, or 125 nm to about 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 1000, 2000, 3000, 4000, 5000, or 6000 nm or more, optionally measured using microscopy (e.g., optical microscopy, confocal microscopy, scanning electron microscopy (SEM), and / or transmission electron microscopy (TEM)) and / or dynamic light scattering (DLS). In certain embodiments, the particles have a size (e.g., diameter) in at least one dimension of about 25, 50, 75, 100, 125, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 1000, 2000, 3000, 4000, 5000, or 6000 nm or more. In certain embodiments, the complexes of the invention in a liquid composition (e.g., an aqueous composition) have an average size (e.g., diameter) of about 50 or 100 nm to about 150, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 2000, 3000, 4000, 5000, or 6000 nm or more. In certain embodiments, the various complexes of the invention, the complexes prepared according to the methods of the invention, and / or the complexes present in the compositions of the invention have a Dv(50) of about 25, 50, 75, 100, 125, 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 1000, 2000, 3000, 4000, 5000, or 6000 nm or more, optionally measured using microscopy (e.g., SEM and / or TEM) and / or DLS.

[0068] In certain embodiments, the complex of the present invention comprises an active ingredient. The active ingredient may be present in (e.g., wrapped and / or encapsulated in) the complex. In certain embodiments, the active ingredient may be bound (e.g., covalently and / or non-covalently) to a protein, anionic biopolymer, and / or cationic biopolymer present in the complex. Exemplary active ingredients include, but are not limited to, amino acids (e.g., tryptophan, leucine, phenylalanine, cysteine, and / or tyrosine), vitamin E, iron, vitamin A, vitamin D, and any combination thereof.

[0069] The complexes of the invention may have improved (e.g., increased) storage, stability (e.g., thermal stability), activity (e.g., antiviral and / or antibacterial activity), and / or function of the biopolymer (e.g., protein, cationic biopolymer, and / or anionic biopolymer) present in the complex, compared to the storage, stability, activity, and / or function of the biopolymer alone (i.e., the biopolymer not present in the complexes of the invention). In certain embodiments, the complexes of the invention provide increased stability for the biopolymer (e.g., protein) present in the complex, compared to the stability of the biopolymer alone.

[0070] In certain embodiments, the solubility of a complex of the invention in a composition (e.g., water, a buffer, milk (e.g., skim milk) and / or an acid whey beverage) remains within about 30% of its original solubility prior to storage (e.g., the solubility of the complex in the composition when the complex is initially formed and / or on the first day of storage) after storage in a closed container at about 4°C to about 25°C for about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12 months. In certain embodiments, the amount of biopolymer (e.g., protein, cationic biopolymer and / or anionic biopolymer) present in a complex of the invention, optionally in a composition (e.g., water, buffer, milk (e.g., skim milk) and / or acid whey beverage) remains within about 30% of the amount of biopolymer present in the complex before storage (e.g., the amount of biopolymer present in the complex when the complex is initially formed and / or on day 1 of storage) after storage in a closed container at about 4°C to about 25°C for about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12 months, optionally measured by chromatography (e.g., high performance liquid chromatography), assay (e.g., ELISA) and / or spectroscopy (e.g., circular dichroism and / or UV-visible). In certain embodiments, after storage in a closed container at about 4°C to about 25°C for about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12 months and optionally in a composition (e.g., water, a buffer, milk (e.g., skim milk) and / or an acid whey beverage), the activity (e.g., biological activity, antiviral activity and / or antibacterial activity) and / or function of the biopolymer (e.g., protein, cationic biopolymer and / or anionic biopolymer) present in the complex of the present invention remains within about 30% of the activity (e.g., biological activity) and / or function of the biopolymer present in the complex prior to storage (e.g., the activity and / or function of the biopolymer present in the complex when the complex is initially formed and / or on day 1 of storage). In certain embodiments, after storage in a closed container at about 4°C to about 25°C for about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12 months and optionally in a composition (e.g., water, a buffer, milk (e.g., skim milk) and / or an acid whey beverage), the physicochemical properties (e.g., turbidity and / or particle size) of the complex of the present invention remain within about 30% of its original physicochemical properties of the complex prior to storage (e.g., the physicochemical properties of the complex when the complex was initially formed and / or on the first day of storage).

[0071] In certain embodiments, the antimicrobial capacity and / or activity (e.g., antibacterial activity and / or antiviral activity against Gram-positive and / or Gram-negative bacteria) of the biopolymers (e.g., proteins, cationic biopolymers and / or anionic biopolymers) present in the complexes of the invention is maintained and / or remains within about 30% of the antimicrobial capacity and / or activity of the biopolymers prior to storage (e.g., the antibacterial and / or antiviral activity of the biopolymers present in the complex when the complex is initially formed and / or on day 1 of storage) after storage in a closed container at about 4°C to about 25°C for about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12 months and optionally in a composition (e.g., water, a buffer, milk (e.g., skim milk) and / or an acid whey beverage).

[0072] In certain embodiments, the complex of the invention is present in a composition (e.g., water, a buffer, milk (e.g., skim milk) and / or an acid whey beverage) stored in a sealed container at about 4°C to about 25°C for about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12 months, and the solubility of the complex in the composition, the retention rate of the biopolymer (e.g., protein, cationic biopolymer and / or anionic biopolymer) in the complex, and / or the activity (e.g., biological activity, such as antibacterial activity and / or antiviral activity) and / or function of the biopolymer (e.g., protein, cationic biopolymer and / or anionic biopolymer) present in the complex are optionally measured at the end of the storage period.

[0073] In certain embodiments, the size (e.g., diameter) of the complex (e.g., particle) of the present invention in at least one dimension remains within ± about 20% of its original size (e.g., size when the complex was initially formed and / or size on day 1 of storage) after storage in a sealed container at about 4°C to about 25°C for about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12 months and optionally in a composition (e.g., water, buffer, milk (e.g., skim milk) and / or acid whey beverage). For example, at an initial time point (e.g., the beginning of the first day of the storage period), the complex (e.g., particle) may have a diameter of about 25 nm to about 6000 nm and after storage in a sealed container at about 4°C to about 25°C for about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12 months from the first day of the storage period, the complex may have a size that increases or decreases by about 20% or less. In certain embodiments, after storage in a sealed container at about 4° C. to about 25° C. for about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12 months, the complex (e.g., particle) of the invention has a size (e.g., diameter) in at least one dimension that increases by less than about 20% compared to its original size. In certain embodiments, the dried complex (e.g., particle) of the invention (e.g., freeze-dried and / or spray-dried particles and / or particles containing water in an amount of about 0% to about 5% (by weight) of the dried particles) is stored in a sealed container at about 4° C. to about 25° C. for about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12 months, and optionally, at the end of the storage period, the size (e.g., diameter) of the dried complex is measured and / or the dried complex is reconstituted (e.g., dissolved and / or dispersed) in a composition (e.g., water and / or a buffer) and the size (e.g., diameter) of the complex in the composition is measured. In certain embodiments, the complexes (e.g., particles) of the invention are present in a composition (e.g., water, a buffer, milk (e.g., skim milk) and / or an acid whey beverage) and stored in a sealed container at about 4°C to about 25°C for about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12 months, and the size (e.g., diameter) of the complexes in the composition is optionally measured at the end of the storage period.

[0074] In certain embodiments, the complex of the present invention provides increased stability for the protein present in the complex after exposure to a temperature in the range of about 70°C or 75°C to about 80°C, 85°C, 90°C, 95°C or 100°C for about 1, 2, 3, 4, 5 or 10 minutes to about 15, 20, 30, 40, 50 or 60 minutes, compared to the stability of the individual protein (i.e., the protein not present in the complex of the present invention) after exposure to the same conditions (e.g., the same temperature for the same period of time). In certain embodiments, the complex can be present in a composition (e.g., water, a buffer, milk (e.g., skim milk) and / or an acid whey beverage) and exposed to the temperature. In certain embodiments, the increased stability of the protein is determined and / or demonstrated by reduced degradation of the protein in the complex compared to the degradation of the individual protein. In certain embodiments, after exposure to a temperature in the range of about 70°C or 75°C to about 80°C, 85°C, 90°C, 95°C or 100°C for about 1, 2, 3, 4, 5 or 10 minutes to about 15, 20, 30, 40, 50 or 60 minutes, the protein present in the complex of the invention is degraded by less than about 30%, such as about 25%, 20%, 15%, 10%, 5%, 1% or less, optionally measured by chromatography (e.g., high performance liquid chromatography), assay (e.g., ELISA) and / or spectroscopy (e.g., circular dichroism). In certain embodiments, the protein present in the complex of the invention is degraded by less than about 30%, such as about 25%, 20%, 15%, 10%, 5%, 1% or less, after exposure to a temperature in the range of about 100°C, 105°C, 110°C, 115°C or 120°C to about 125°C, 130°C, 135°C, 140°C or 145°C for about 2, 5, 10, 20 or 30 seconds to about 40, 50 or 60 seconds (e.g., high temperature short time (HTST) or ultra high temperature (UHT) treatment at about 145°C for about 2 seconds to about 60 seconds), optionally measured by chromatography (e.g., high performance liquid chromatography), assay (e.g., ELISA) and / or spectroscopy (e.g., circular dichroism). In certain embodiments, the protein present in the complexes of the invention is degraded by less than about 20%, such as about 15%, 10%, 5%, 1% or less, after exposure to a temperature in the range of about 100°C, 105°C, 110°C, 115°C or 120°C to about 125°C, 130°C, 135°C, 140°C or 145°C for about 2, 5, 10, 20 or 30 seconds to about 40, 50 or 60 seconds (e.g., high temperature short time (HTST) or ultra high temperature (UHT) treatment at about 145°C for about 2 seconds to about 60 seconds), optionally measured by chromatography (e.g., high performance liquid chromatography), assay (e.g., ELISA) and / or spectroscopy (e.g., circular dichroism).

[0075] In certain embodiments, the antimicrobial capacity and / or activity (e.g., antibacterial activity against Gram-positive and / or Gram-negative bacteria and / or antiviral activity) of the protein present in the complex of the present invention after exposure to a temperature in the range of about 70°C or 75°C to about 80°C, 85°C or 90°C for about 30 seconds to about 2 minutes is retained and / or improved (e.g., increased) compared to the antimicrobial capacity and / or activity of the individual protein, optionally after exposure to the same conditions (e.g., the same temperature and time). In certain embodiments, the complex can be present in a composition (e.g., water, a buffer, milk (e.g., skim milk) and / or an acid whey beverage) and exposed to the temperature. In certain embodiments, the antimicrobial capacity and / or activity (e.g., antibacterial activity against Gram-positive and / or Gram-negative bacteria and / or antiviral activity) of a protein present in a complex of the invention after exposure to a temperature in the range of about 70°C or 75°C to about 80°C, 85°C or 90°C for about 30 seconds to about 2 minutes is retained and / or increased compared to the antimicrobial capacity and / or activity of the protein alone, optionally after exposure to the same conditions (e.g., the same temperature and time).

[0076] In certain embodiments, the solubility of a complex of the invention in a composition (e.g., water, a buffer, milk (e.g., skim milk) and / or an acid whey beverage) remains within about 30% of its original solubility prior to exposure (e.g., the solubility of the complex in the composition when the complex is initially formed and / or immediately prior to exposure) after exposure to a temperature in the range of about 70°C or 75°C to about 80°C, 85°C or 90°C for about 30 seconds to about 2 minutes, or to a temperature in the range of about 100°C, 105°C, 110°C, 115°C or 120°C to about 125°C, 130°C, 135°C, 140°C or 145°C for about 2, 5, 10, 20 or 30 seconds to about 40, 50 or 60 seconds. In certain embodiments, exposure to a temperature in the range of about 70°C or 75°C to about 80°C, 85°C, or 90°C for about 30 seconds to about 2 minutes, or exposure to a temperature in the range of about 100°C, 105°C, 110°C, 115°C, or 120°C to about 125°C, 130°C, 135°C, 140°C, or 145°C for about 30 seconds to about 2 minutes, is less than the amount of biopolymer present in the complex prior to exposure (e.g., the amount of biopolymer present in the complex when the complex is initially formed and / or immediately prior to exposure). After about 2, 5, 10, 20 or 30 seconds to about 40, 50 or 60 seconds, the amount of biopolymer (e.g., protein, cationic biopolymer and / or anionic biopolymer) present in the complex of the present invention in the composition (e.g., water, buffer, milk (e.g., skim milk) and / or acid whey beverage) remains within about 30%, optionally measured by chromatography (e.g., high performance liquid chromatography), assay (e.g., ELISA) and / or spectroscopy (e.g., circular dichroism and / or UV-visible). In certain embodiments, the activity (e.g., biological activity, antiviral activity, and / or antibacterial activity) and / or function of the biopolymer (e.g., protein, cationic biopolymer, and / or anionic biopolymer) present in the complex of the present invention in a composition (e.g., water, buffer, milk (e.g., skim milk) and / or acid whey beverage) is enhanced upon exposure of the composition to a temperature in the range of about 70°C or 75°C to about 80°C, 85°C, or 90°C for about 30 seconds to about 2 minutes or exposure to about 100°C. , 105°C, 110°C, 115°C or 120°C to about 125°C, 130°C, 135°C, 140°C or 145°C after about 2, 5, 10, 20 or 30 seconds to about 40, 50 or 60 seconds of the activity (e.g., biological activity) and / or function of the biopolymer present in the complex prior to exposure (e.g., the activity and / or function of the biopolymer present in the complex when the complex is initially formed and / or immediately prior to exposure).In certain embodiments, the physicochemical properties (e.g., turbidity and / or particle size) of a complex of the invention present in a composition (e.g., water, a buffer, milk (e.g., skim milk) and / or an acid whey beverage) remain within about 30% of its original physicochemical properties of the complex prior to exposure (e.g., the physicochemical properties of the complex when the complex is initially formed and / or immediately prior to exposure) after exposure to a temperature in the range of about 70°C or 75°C to about 80°C, 85°C or 90°C for about 30 seconds to about 2 minutes, or to a temperature in the range of about 100°C, 105°C, 110°C, 115°C or 120°C to about 125°C, 130°C, 135°C, 140°C or 145°C for about 2, 5, 10, 20 or 30 seconds to about 40, 50 or 60 seconds.

[0077] In certain embodiments, the antimicrobial capacity and / or activity (e.g., antibacterial activity and / or antiviral activity against Gram-positive and / or Gram-negative bacteria) of the biopolymers (e.g., proteins, cationic biopolymers and / or anionic biopolymers) present in the complexes of the present invention in the compositions (e.g., water, buffer, milk (e.g., skim milk) and / or acid whey beverages) is enhanced upon exposure to a temperature in the range of about 70°C or 75°C to about 80°C, 85°C or 90°C for about 30 seconds to about 2 minutes or exposure to The antimicrobial capacity and / or activity of the biopolymer prior to exposure (e.g., the antibacterial and / or antiviral activity of the biopolymer present in the composite when the composite is initially formed and / or immediately prior to exposure) is retained and / or maintained within about 30% after about 2, 5, 10, 20 or 30 seconds to about 40, 50 or 60 seconds at a temperature in the range of about 100°C, 105°C, 110°C, 115°C or 120°C to about 125°C, 130°C, 135°C, 140°C or 145°C.

[0078] In certain embodiments, the complexes of the invention increase the thermal stability of a biopolymer (e.g., a protein, a cationic biopolymer, and / or an anionic biopolymer) present in the complex compared to the thermal stability of the biopolymer alone. For example, the presence of the biopolymer in the complex can reduce or avoid denaturation (e.g., thermal denaturation, such as thermal denaturation during the preparation of a food product comprising the biopolymer) compared to the amount of denaturation of the biopolymer alone (i.e., a biopolymer not present in the complexes of the invention) under the same conditions. In certain embodiments, the complexes of the invention increase the thermal stability of lactoferrin present in the complex after exposure to a temperature for a period of time (e.g., a temperature in the range of about 70°C or 75°C to about 80°C, 85°C, 90°C, 95°C, or 100°C for about 1, 2, 3, 4, 5, or 10 minutes to about 15, 20, 30, 40, 50, or 60 minutes) compared to the thermal stability of lactoferrin alone after exposure to the same conditions (e.g., the same temperature and time). In certain embodiments, the complexes of the invention increase the stability (e.g., thermal stability), structure, activity and / or function of a biopolymer (e.g., lactoferrin) present in the complex after exposure to a pH in the range of about 6.5 to about 7.5, compared to the stability, structure, activity and / or function of the biopolymer alone after exposure to the same conditions (e.g., the same pH).

[0079] The activity and / or function of the biopolymer (e.g., protein, cationic biopolymer and / or anionic biopolymer) present in the complex of the present invention can be increased compared to the activity and / or function of the biopolymer alone. For example, after storing the complex of the present invention for a period of time (e.g., storing the dried complex in a sealed container at a temperature in the range of about 20° C. to about 30° C. for about 1, 2, 3, 4, 5, or 6 months) and / or heating the complex (e.g., maintaining a temperature in the range of about 70° C. or 75° C. to about 80° C., 85° C., 90° C., 95° C. or 100° C. for about 1, 2, 3, 4, 5, or 10 minutes to about 15, 20, 30, 40, 50, or 60 minutes), the biopolymer (e.g., protein) present in the complex can have an increased activity and / or function compared to the activity and / or function of the biopolymer alone after the same storage and / or heating conditions. For example, a complex comprising lactoferrin, an anionic biopolymer, and a cationic biopolymer can provide increased activity and / or function (e.g., increased antimicrobial activity) after storage and / or heating of the complex compared to the activity and / or function of lactoferrin under the same storage and / or heating conditions. In certain embodiments, the complex of the present invention does not contain agents for maintaining and / or stabilizing the activity, function, and / or stability (e.g., thermal stability) of the protein (e.g., lactoferrin) present in the complex, in addition to the anionic biopolymer and / or cationic biopolymer.

[0080] In certain embodiments, the complexes of the invention can provide increased bioavailability for a biopolymer (e.g., a protein, a cationic biopolymer, and / or an anionic biopolymer) present in the complexes of the invention, compared to the bioavailability of the biopolymer alone. The bioavailability can be determined after administering the complex to a subject, optionally wherein administration comprises ingestion of the complex by the subject. In certain embodiments, the biopolymer present in the complexes of the invention has increased bioavailability in the intestinal tract of a subject, compared to the bioavailability of the biopolymer alone. In certain embodiments, the biopolymer present in the complexes of the invention has reduced enzymatic hydrolysis (e.g., reduced enzymatic hydrolysis during the gastric digestion stage of a subject), compared to the amount of enzymatic hydrolysis of the biopolymer alone.

[0081] According to certain embodiments, a composition comprising a complex of the present invention is provided and / or an article comprising a complex of the present invention is provided. In certain embodiments, the composition and / or article comprises a plurality of complexes of the present invention. In certain embodiments, the composition and / or article comprises a complex of the present invention and a carrier. The carrier may be a liquid, such as, but not limited to, water and / or oil. In certain embodiments, the composition of the present invention is an aqueous composition. In certain embodiments, the composition of the present invention is a suspension, optionally wherein the complex of the present invention is suspended in the composition. In certain embodiments, the complex of the present invention stabilizes a composition comprising the complex, optionally wherein the composition is an emulsion. In certain embodiments, the carrier is a solid (e.g., microparticles and / or powder) and a plurality of complexes of the present invention may be present with the solid, optionally present above, below, combined with and / or mixed with the solid. In certain embodiments, the carrier is a food grade component, such as, but not limited to, milk, milk beverages, infant formula and / or instant beverage powder. One or more excipients such as, but not limited to, gum arabic, sodium caseinate, maltodextrin may be present in the composition of the present invention.

[0082] In certain embodiments, the compositions and / or articles of the present invention are food products, nutritional supplements, therapeutic drinks and / or cosmetics. In certain embodiments, the complexes of the present invention may be present in food products. In certain embodiments, the food products are dairy products (e.g., milk, yogurt, etc.). In certain embodiments, the compositions are infant formulas and / or nutritional supplements (optionally beverages).

[0083] In certain embodiments, the turbidity of the composition of the present invention remains within about 30% of the original turbidity of the composition before storage (e.g., the turbidity when the composition is initially formed and / or on the first day of storage), optionally measured by spectroscopy such as ultraviolet-visible (UV-vis) spectroscopy, after storage in a sealed container at about 4°C to about 25°C for about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12 months. In certain embodiments, the composition of the present invention has no or minimal undesirable organoleptic properties (e.g., undesirable tastes such as sour and / or bitter, undesirable color, undesirable appearance, and / or undesirable texture) after storage in a sealed container at about 4°C to about 25°C for about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12 months.

[0084] According to certain embodiments of the present invention, a method for preparing a complex of the present invention is provided. In certain embodiments, the method comprises providing a composition comprising a protein, an anionic biopolymer, and a cationic biopolymer at a pH ranging from about 3, 3.5 or 4 to about 4.5 or 5; and mixing the composition, thereby providing the complex. The composition comprising a protein, an anionic biopolymer, and a cationic biopolymer can be an aqueous composition, and the aqueous composition optionally includes a buffer. In certain embodiments, the composition for preparing the complex of the present invention has a pH of about 3, 3.5, 4, 4.5, or 5. In certain embodiments, the composition for preparing the complex of the present invention comprises a salt, optionally wherein the composition comprises a salt in an amount of about 0.1, 0.5, 1, or 5 mM to about 10, 15, 20, 25, or 30 mM. In certain embodiments, the composition for preparing the complex of the present invention comprises a salt in an amount of about 0.1, 0.5, 1, 5, 10, 15, 20, 25, or 30 mM.

[0085] The composition used to prepare the complex of the present invention can include a protein, an anionic biopolymer and / or a cationic biopolymer in an amount that is each independently about 0.01%, 0.1%, 0.5%, 1%, 2%, 3%, 4% or 5% to about 6%, 7%, 8%, 9% or 10% (by weight) of the composition. In certain embodiments, the composition used to prepare the complex of the present invention includes a protein, an anionic biopolymer and / or a cationic biopolymer in an amount that is each independently about 0.01%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10% (by weight) of the composition. In certain embodiments, the composition for preparing the complex of the present invention may include a protein, an anionic biopolymer and / or a cationic biopolymer, each of which is independently about 0.01%, 0.1%, 0.5%, 1%, 2% or 3% (by weight) of the composition. In certain embodiments, the composition for preparing the complex of the present invention includes an anionic biopolymer and a protein in a weight ratio of about 0.5:1 to about 1:5 (anionic biopolymer: protein), such as a weight ratio of about 0.5:1, 1:1, 1:2, 1:3, 1:4 or 1:5 (anionic biopolymer: protein). In certain embodiments, the composition for preparing the complex of the present invention includes a protein and a cationic biopolymer in a weight ratio of about 1:1 to about 10:1 (protein: cationic biopolymer), such as a weight ratio of about 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10 (protein: cationic biopolymer). In certain embodiments, the composition used to prepare the complex of the invention comprises anionic biopolymers, proteins, and cationic biopolymers in a weight ratio of about 1:3:1, about 4:5:1, or about 3:6:1 (anionic biopolymer:protein:cationic biopolymer). In certain embodiments, the composition used to prepare the complex of the invention has a total concentration of proteins, anionic biopolymers, and cationic biopolymers in the composition in an amount of about 10% (by weight) or less of the composition, such as about 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, or 10% (by weight) of the composition.In certain embodiments, the composition used to prepare the complexes of the invention has a total concentration of protein, anionic biopolymer, and cationic biopolymer in the composition in an amount of about 5% (by weight) or less of the composition, such as about 0.05%, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5% (by weight) of the composition.

[0086] Mixing the composition for preparing the composite of the present invention can be accomplished using methods known in the art. In certain embodiments, mixing the composition for preparing the composite of the present invention comprises mixing the composition for about 15, 20, 25 or 30 minutes to about 35, 40, 45, 50, 55 or 60 minutes, optionally at a temperature in the range of about 20°C, 25°C or 30°C to about 35°C, 40°C, 45°C, 50°C, 55°C or 60°C.

[0087] In certain embodiments, the methods of the present invention comprise forming an intermediate composition comprising a protein and an anionic biopolymer, optionally wherein the intermediate composition is an aqueous composition. In certain embodiments, the methods of the present invention comprise combining anionic biopolymers and proteins to provide an intermediate composition (optionally an aqueous composition) and mixing the intermediate composition to optionally form an intermediate complex comprising anionic biopolymers and proteins. In certain embodiments, mixing the intermediate composition can be performed for about 15, 20, 25 or 30 minutes to about 35, 40, 45, 50, 55 or 60 minutes, optionally at a temperature in the range of about 20°C, 25°C or 30°C to about 35°C, 40°C, 45°C, 50°C, 55°C or 60°C. The method may further comprise adding a cationic biopolymer to the intermediate composition to provide a composition comprising anionic biopolymers and proteins (optionally in the form of an intermediate complex) and further comprising the cationic biopolymer, and mixing the composition to form the complex.

[0088] The method of the present invention may further comprise hardening the composite of the present invention. In certain embodiments, hardening the composite comprises adjusting the temperature of the composition comprising the composite of the present invention to a temperature in the range of about 5°C to about 10°C and exposing the composition to a temperature in the range of about 5°C to about 10°C for about 1 or 2 hours to about 3, 4, 5 or 6 hours.

[0089] In certain embodiments, the method of the present invention comprises separating and / or obtaining the complex of the present invention from a composition. Separating and / or obtaining the complex of the present invention from a composition may comprise centrifuging, drying, freeze drying, filtering and / or spray drying the composition to separate and / or obtain the complex. In certain embodiments, the separated and / or obtained complex is a dried complex, optionally wherein the dried complex comprises water in an amount of about 0% to about 5% (by weight) of the dried complex. The dried complex may be in the form of microparticles and / or powders. In certain embodiments, the separated and / or obtained complex is ground, milled and / or micronized to provide a desired size, such as particles having a size (e.g., diameter) of less than about 1 mm. In certain embodiments, the complex of the present invention may be cross-linked using a cross-linking agent such as, but not limited to, transglutaminase, glyceraldehyde, dialdehyde pectin and / or genipin. In the complex of the present invention, proteins, cationic biopolymers and / or anionic biopolymers may be cross-linked.

[0090] In certain embodiments, the method of the present invention comprises combining the complex of the present invention with a carrier, optionally wherein the carrier is a liquid or solid. In certain embodiments, the complex of the present invention is added to a food-grade component and / or added to a food product (e.g., a beverage or powder formulation). Combining the complex of the present invention with a carrier may comprise mixing the separated and / or obtained complex into a carrier and / or mixing the complex of the present invention present in a composition (e.g., an aqueous composition) into a carrier. In certain embodiments, the complex of the present invention is optionally dispersed in a carrier by mixing, stirring, homogenizing, etc. at a temperature in the range of about 20°C, 25°C or 30°C to about 35°C, 40°C, 45°C, 50°C, 55°C or 60°C.

[0091] The methods of the invention may comprise providing a therapeutic effect and / or benefit to a subject and / or treating and / or preventing a disease, disorder and / or condition in a subject. The methods may comprise administering (e.g., orally administering) a complex of the invention and / or a composition of the invention to a subject, optionally wherein the administration comprises ingestion of the complex and / or composition by the subject.

[0092] In certain embodiments, the methods of the present invention comprise administering to a subject a therapeutically effective amount of a complex of the present invention and / or a composition of the present invention. As used herein, the term "therapeutically effective amount" means an amount of a complex of the present invention and / or a composition that induces a therapeutically useful response in a subject. It will be appreciated by those skilled in the art that the therapeutic effect need not be complete or curative, as long as some benefit is provided to the subject.

[0093] As used herein, "treatment" or "treating" (and grammatical variations thereof) means any type of treatment that provides a benefit to a subject, and may refer to a reduction in severity, at least partial improvement or amelioration of the subject's condition, and / or a certain degree of relief, alleviation or reduction of at least one clinical symptom associated with the subject's condition, and / or a delay in the progression of symptoms. In certain embodiments, the severity of symptoms associated with iron deficiency in a subject may be reduced compared to the severity of the symptoms in the absence of the methods of the invention. In certain embodiments, the complexes of the invention and / or compositions of the invention are administered to a subject to improve iron delivery and / or adsorption in the subject and / or to treat a disease and / or its symptoms.

[0094] In certain embodiments, the complexes of the invention and / or compositions of the invention may be administered in a therapeutically effective amount. As used herein, a "therapeutically effective" amount is an amount sufficient to treat (as defined herein) a subject. Those skilled in the art will appreciate that the therapeutic effect need not be complete or curative, as long as some benefit is provided to the subject. In certain embodiments, a therapeutically effective amount may be achieved by administering to a subject a complex and / or composition of the invention, optionally wherein said administration comprises ingestion of said complex and / or composition by said subject.

[0095] The terms "prevent" and "preventing" (and grammatical variations thereof) mean avoiding, reducing and / or delaying the onset of symptoms associated with a disease, disorder or condition, and / or reducing the severity of the onset of symptoms associated with a disease, disorder or condition relative to what would occur in the absence of the methods of the invention. Prevention can be complete, such as a complete absence of symptoms. Prevention can also be partial, such that the occurrence and / or severity of the onset of symptoms in a subject is less than what would occur in the absence of the methods of the invention. In certain embodiments, a complex of the invention and / or a composition of the invention is administered to a subject to prevent a disease, disorder or condition.

[0096] In certain embodiments, the complex of the present invention and / or the composition of the present invention can be administered in a preventive effective amount. As used herein, a "preventive effective" amount is an amount sufficient to prevent (as defined herein) symptoms associated with a disease, disorder or condition in a subject. Those skilled in the art will appreciate that the level of prevention does not need to be complete, as long as some benefit is provided to the subject. In certain embodiments, a preventive effective amount can be achieved by administering to a subject a complex and / or composition of the present invention, optionally wherein said administration comprises ingestion of said complex and / or composition by said subject.

[0097] The present invention can be used for veterinary and medical applications. Subjects suitable for treatment with the methods of the present invention include, but are not limited to, mammalian subjects. Mammals of the present invention include, but are not limited to, canines, felines, bovines, goats, equines, sheep, pigs, rodents (e.g., rats and mice), lagomorphs, primates (e.g., apes and humans), non-human primates (e.g., monkeys, baboons, chimpanzees, gorillas), etc. and mammals in utero. Any mammalian subject that needs to be treated according to the present invention is applicable. According to the present invention, human subjects of both sexes and at any stage of development (i.e., newborns, infants, teenagers, adolescents, adults) can be treated. In certain embodiments of the present invention, the subject is a mammal, and in certain embodiments, the subject is a human. Human subjects include males and females of all ages, including fetuses, newborns, infants, teenagers, adolescents, adults and elderly subjects, as well as pregnant subjects. In a specific embodiment of the present invention, the subject is a teenager and / or an adult.

[0098] The methods of the invention may also be performed on animal subjects, particularly mammalian subjects such as mice, rats, dogs, cats, livestock and horses for veterinary purposes, and / or for drug screening and drug development purposes.

[0099] In certain embodiments, the subject is "in need of" or "in need of" the methods of the invention, e.g., the subject has findings typically associated with a disease, disorder, or condition, is suspected of having a disease, disorder, or condition, and / or the subject has a disease, disorder, or condition.

[0100] The present invention will now be described with reference to the following examples. It should be understood that these examples are not intended to limit the scope of the claims of the present invention, but are intended to illustrate certain embodiments. Any changes in the exemplary methods that a skilled person would expect are intended to fall within the scope of the present invention. Example

[0101] Embodiment 1:

[0102] The effective delivery of the bioactive protein lactoferrin (LF) remains a challenge as it is sensitive to environmental changes and easily denatured during heating, limiting its application in functional foods. To overcome these challenges, polyelectrolyte ternary complexes of LF with gelatin (G) and negatively charged polysaccharides were formulated. Linear, highly charged polysaccharides were able to form interpolymer complexes with LF and G, whereas aggregates were formed with branched polysaccharides. Unique multiphase aggregates were observed in the gum arabic GA-LF-G complexes, in which a unique aggregate-in-aggregate structure was found. Ternary complexes made with GA, soy soluble polysaccharide (SSP), or high methoxyl pectin (HMP) retained the protein structure and exhibited enhanced thermal stability of LF. The GA-LF-G complex was particularly stable, with >90% retention of native LF after treatment at 90°C for 2 min or at 145°C for 30 s in a water bath, while the LF control had only about 7% of undenatured LF under both conditions. Compared to untreated LF, LF in the ternary complex retains significant antibacterial activity against Gram-positive and Gram-negative bacteria even after heat treatment. These ternary complexes of LF retain the desired functionality, thermal stability and antibacterial activity of LF in the final product. The ternary complex structure, especially the multiphase aggregates, can serve as a template for encapsulation and stabilization of other bioactive substances and peptides.

[0103] 1. Introduction

[0104] This article reports the preparation of ternary complexes of positively charged LF and G with five different negatively charged polysaccharides to determine whether the complexes can improve the structural stability and / or antibacterial activity of LF during thermal treatment. As described below, the complexes formed by polysaccharides with different charge density and chain flexibility showed different structural and thermal stabilities. The physicochemical properties of these ternary complexes were studied using turbidity, zeta potential and particle size as well as microscopic analysis. The structural changes and retention ratios of LF after thermal treatment were then evaluated by intrinsic fluorescence, circular dichroism (CD) spectroscopy, SDS-PAGE and HPLC.

[0105] 2. Materials and Methods

[0106] 2.1 Materials

[0107] Bovine lactoferrin (LF) (Bioferrin 2000, iron>15mg / 100g) was obtained from Glanbia Nationals, Inc. (Fitchburg, WI, USA). Soybean soluble polysaccharide (SSP) was provided by Fuji Oil (Izumisano-shi, Japan). High methoxyl pectin (HMP), Kappa carrageenan (Kappa) and Iota carrageenan (Iota) were provided by Tic gum (Riverside, MD, USA). Gum Arabic (GA) was provided by Colony Gum (Monroe, NC, USA). Gelatin (Knox unflavored gelatin) was purchased from a local grocery store (Target, Ithaca, NY, USA). Fluorescein isothiocyanate isomer I (FITC) was purchased from Sigma-Aldrich (St. Louis, MO, USA). Trifluoroacetic acid, acetonitrile (HPLC grade), hydrochloric acid, sodium hydroxide, and dimethyl sulfoxide (DSMO) were purchased from Fisher Scientific (Hampton, NH, USA). Reagents for SDS-PAGE were purchased from Bio-Rad Laboratories (Hercules, CA, USA). Bicinchoninic acid (BCA) assay kit II was purchased from BioVision (Waltham, MA, USA). Coomassie brilliant blue G-250 was purchased from bioWORLD (Dublin, OH, USA). Luria broth (LB) and LB agar were purchased from Sigma-Aldrich (St. Louis, MO, USA). Other chemicals and reagents were purchased from Fisher Scientific (Hampton, NH, USA).

[0108] 2.2 Preparation of ternary complex

[0109] LF, SSP and GA solutions were prepared at 1% or 0.2% (w / v) by dissolving the biopolymers in Milli-Q water and mixed at room temperature (25°C) for 2 hours. HMP, Kappa and Iota solutions were prepared at 0.2% (w / v) by dissolving the biopolymers in Milli-Q water and heated to at least 60°C and mixed for 2 hours. Gelatin (G) solutions were prepared at 1% or 0.2% (w / v) by dissolving the biopolymers in Milli-Q water and mixed at 45°C for 2 hours. All solutions were cooled to 4°C and allowed to stand overnight to ensure adequate hydration.

[0110] Figure 1 The use of branched polysaccharides ( Figure 1 , panel a) and linear polysaccharides ( Figure 1, inset b) is an exemplary schematic diagram of the ternary complex formation procedure. By adding the same concentration of biopolymer solution in a ratio, a ternary complex with a total concentration of 1% or 0.2% (w / v) was prepared. The addition ratio of the biopolymer was designed according to the ternary diagram, with a ratio interval of 10% (mass ratio of the total biopolymer). First, all biopolymer solutions were adjusted to a target pH of pH 4 or pH 7. These pH levels were selected to represent the pH when LF has a high positive charge (pH 4) and a low positive charge (pH 7). Then, the different polysaccharide solutions were first mixed with the LF solution at room temperature (25°C) for 30 minutes to form an intermediate complex. The mixture was then heated to 45°C and mixed with the preheated gelatin solution at 45°C for another 30 minutes. After all biopolymers were thoroughly mixed, the solution was hardened at 10°C for 2 hours. In order to separate the complex, the ternary mixture was centrifuged at 10,000g for 25 minutes at 4°C. The precipitate was collected and frozen (-20° C.) overnight and then freeze-dried for 48-36 hours using a freeze dryer (Labcono, Kansas, MO, USA) with a vacuum pressure of -0.175 mbar and a moisture collector temperature of -53° C. The supernatant was collected and stored at 4° C. for recombination efficiency measurements.

[0111] 2.3 Characterization of the complex

[0112] 2.3.1 Turbidity measurement

[0113] The turbidity of the ternary mixture was measured using an ultraviolet-visible spectrophotometer (UV-2600, SHIMADZU Co., Japan). The transmittance was measured at 600 nm in a 1 cm path length quartz cuvette at room temperature. Milli-Q water was used as a blank (100% transmittance). Turbidity (T) was calculated according to the following equation (Equation 1):

[0114]

[0115] Where I is the transmittance intensity of the sample, and I0 is the transmittance intensity of the blank.

[0116] 2.3.2 Particle size measurement

[0117] The mean diameter and particle size distribution of the ternary mixture were analyzed using a dynamic light scattering instrument (Zetasizer Nano-ZS, Malvern, Germany). All analyses were performed at 25°C in a 1-cm path length cuvette, with a wavelength of 633 nm and a backscattering angle of 173°. The refractive index of the dispersant was set to 1.33, and the refractive index of the material was set to 1.45. The analysis was performed in triplicate, with each measurement run at least 11 times.

[0118] 2.3.3 Zeta potential measurement

[0119] The zeta potential of the ternary mixture was measured using Nano-ZS (Malvern, Germany) using the Smouluchwski mode. The software can determine the appropriate measurement type after obtaining the sample conductivity using a voltage of about 150 V. The samples were measured in triplicate, with each measurement run 10 times.

[0120] 2.3.5 Morphological characterization

[0121] 2.3.5.1. Confocal microscopy analysis

[0122] For imaging purposes, LF was labeled with FITC (fluorescein isothiocyanate) using the following procedure. LF was dissolved in 10mM carbonate buffer (pH 10.0) at 5w / v%. FITC was dissolved in DMSO at 10w / v%. The LF solution was mixed with FITC at a volume ratio of 20:1 at room temperature in the dark for 3 to 4 hours. The mixture was washed through a gel filtration column (filled with Sephadex G-25) to remove excess FITC. The green-yellow solution was collected from the column and the labeled protein was confirmed by UV-visible spectroscopy. The resulting FTIC-labeled LF solution was freeze-dried for subsequent ternary complex and confocal microscopy analysis.

[0123] Confocal microscopy images of ternary complexes made with FTIC-labeled LF were obtained using a Zeiss LSM 710 confocal laser scanning microscope connected to an Inverted Axio Observer.Z1 microscope using a 40× water immersion objective (NA1.2). A small portion of the complex solution was transferred to a glass microscope slide and covered with a glass cover slip. With the green (confocal) image, we used an excitation argon laser (488 nm) and detection light between 500-559 nm to observe the LF in the complex. Conventional optical images were taken by turning off the laser and turning on conventional white polarized light. Images were analyzed by the instrument software (EZCS1 version 3.8, Niko, Melville, NY).

[0124] 2.3.5.2. Scanning electron microscopy analysis

[0125] The microstructure of the LF ternary complex was observed using a field emission scanning electron microscope (SEM) (Zeiss Gemini 500, Jena, Germany) by the method described by (Lin et al., 2022). Before taking microscopy images, fresh ternary mixture samples (about 10 μL) were vacuum dried overnight and then coated with Au / Pd in ​​a sputter coater (Denton Desk V, NJ, USA).

[0126] 2.3.6 Measurement of LF composite efficiency and load ratio

[0127] The supernatant obtained after centrifugation of the ternary mixture was appropriately diluted and used to quantify free LF according to the Bradford method (Bradford, 1976).

[0128] Formula 2) calculates the composite efficiency:

[0129]

[0130] Total LF is the theoretical concentration (w / v%) of LF used in the ternary mixture; free LF is the measured concentration (w / v%) of LF in the supernatant.

[0131] The freeze-dried complex samples were weighed for yield measurement, which was calculated according to the following equation (Equation 3):

[0132]

[0133] The loading ratio (mass ratio) of LF in the freeze-dried complex samples was quantified using the BCA assay in the redispersed complex samples at a concentration of 0.2 w / v% in PBS buffer pH 7. The loading ratio of LF in the freeze-dried complex was calculated according to the following equation (Equation 4):

[0134]

[0135] 2.3.7 Thermal stability test of LF in ternary complex

[0136] Samples including pure LF and rehydrated ternary complex solution in water or PBS buffer at pH 7 (10 mM; 0.2 w / v%) were loaded into glass test tubes (2 mL) and placed in water baths at different temperatures of 75°C or 90°C for 2 minutes, and then immersed in an ice-water bath to cool to ambient temperature (T = 25°C) before further analysis. The samples were also treated at 145°C using an oil bath and treated at this temperature for 2 seconds, 10 seconds, 30 seconds and 60 seconds. Optical images, turbidity and particle size of the ternary complex solution before and after heat treatment were obtained. The structural changes of the protein during heating were understood by analyzing intrinsic fluorescence and circular dichroism spectra. Electrophoretic analysis and HPLC analysis were used to quantify the LF retention ratio after heat treatment.

[0137] 2.3.8 Electrophoresis analysis

[0138] In vertical microgel electrophoresis system (Mini-PRO-TEAN Tetra cell, Bio-Rad, the U.S.), sodium dodecyl sulfate (SDS)-PAGE was used to analyze unheated and heated LF and ternary complex samples. The premixed TGA fast casting acrylamide entry kit was used to prepare PAGE gel. 20 microliters of diluted samples (2mg / mL of protein) were mixed with 2X Laemmli buffer at a ratio of 1:1, and then heated in a boiling water bath for 5 minutes. Then, 20 μL of mixture was loaded onto the gel and electrophoresed (200V) for about 30-45 minutes. The gel was stained for half an hour in a 0.15% (w / v) Coomassie Brilliant R-250 solution consisting of 50% (v / v) methanol and 10% (v / v) acetic acid. Then, the gel was decolorized in a decolorizing solution (20% (v / v) methanol and 10% (v / v) acetic acid) for 24 hours.

[0139] 2.3.9 HPLC analysis

[0140] Developed HPLC analysis to quantify the undenatured LF in the complex solution after heat treatment. All samples were top liquid solutions to avoid protein aggregates and filtered through a 0.45 μm filter. Reverse phase HPLC was performed on an Agilent 1100 / 1200 series HPLC system (Agilent Technologies, CA, USA) equipped with a diode array detector and ChemStation data acquisition program. Detection was performed at 214nm. LF separation was performed at 40°C using a BioZen Intact XB-C8 column (150x 4.6mm, 3.6m; Phenomenex, Torrance CA, USA). Gradient elution was performed using 0.1% trifluoroacetic acid (TFA) aqueous solution (A) and 0.1% trifluoroacetic acid acetonitrile solution (B), with a mobile phase flow rate of 1.0 mL / min, using the following gradient elution: 0-5 minutes, 5% B; 5-20 minutes, 5-20% B; 20-25 minutes, 50-5% B. The injection volume was 10 μL. According to the standard curve of natural LF with a concentration of 0-0.2 w / v% (R 2 >99%), the concentration of native LF remaining in the sample solution can be measured and quantified. The LF retention ratio is calculated using the following equation, which indicates how much LF remains in the native state after heat treatment in the complex solution:

[0141]

[0142] 2.3.10 Circular dichroism (CD) spectroscopy analysis

[0143] The secondary structure of lactoferrin in pure LF and ternary complex solutions before and after heat treatment was measured using CD spectroscopy. The CD spectra of LF and the redispersed complex were measured in the far-UV region (190-260 nm) at 25°C using an AVIV-202-01 spectropolarimeter (Lakewood, NJ, USA). To reduce the gain, the samples were diluted to 0.02% (w / w) LF before the measurement. The samples were analyzed in a quartz cuvette with a 1-mm path length. The obtained data were converted into molar ellipticity [θ] (degrees cm) using the DichroWeb online processing platform. 2 dmol -1 ). Pure gelatin showed no secondary structure based on its limited CD spectral signals; therefore, the CD spectrum of the ternary complex was mainly referenced to the secondary structure of LF.

[0144] 2.3.11 Intrinsic fluorescence analysis

[0145] The intrinsic fluorescence of LF and ternary complex samples before and after heat treatment was measured using a Shimadzu RF-6000 spectrophotometer (Shimadzu, Japan). The samples were measured at an excitation wavelength of 280 nm in a 1-cm quartz cuvette, and the emission was monitored in the range of 310-400 nm; the excitation / emission slit widths were both set at 10 nm.

[0146] 2.3.12 Antimicrobial activity analysis

[0147] In this study, Staphylococcus aureus strains and Escherichia coli (E. coli) strains were used as target Gram-positive bacteria and Gram-negative bacteria, respectively. Staphylococcus aureus strains were isolated from cattle feces by the Animal Health Diagnostic Center (AHDC) of Cornell University. Escherichia coli (k12 Mg1655) strains were obtained from the American Type Culture Collection (ACTT) (Freddolino et al., 2012). First, frozen bacteria were activated in Luria broth (LB) agar medium. Then a loop of pure colonies was transferred to fresh LB medium and incubated at 37°C for 24 hours for further antibacterial activity measurement.

[0148] Antibacterial activity was measured on a 96-well microtiter plate using the UV absorbance method. First, the bacterial Staphylococcus aureus or Escherichia coli was diluted 1000 times in LB liquid medium to ensure that the absorbance of 100 μl of bacterial liquid medium at 625nm was less than 0.04. The increase in absorbance (OD 625nm) at 625nm was used to indicate bacterial growth. In order to conduct MIC (minimum inhibitory concentration) studies, LFs of different dilution concentrations (0.1-1% w / v) were used. The volume of 100 μL of diluted bacterial liquid medium and 100 μL of LF solution was added to each well. Then, 100 μL of bacterial liquid medium and 100 μL of PBS buffer were used as controls. The lowest concentration of LF that inhibited 50% bacterial growth (i.e. 50% of the OD value of the control group) was used as the concentration for further antibacterial studies of the LF ternary complex study. Similarly, based on MIC studies, 100 μL of diluted bacterial broth and 100 μL of selected concentrations (0.2%, w / v) of unheated and heated LF complex solutions were added to each well. The microtiter plates were incubated at 37°C and OD625nm was measured to monitor bacterial growth at 0, 24 and 48 hours of incubation, with shaking for 10 seconds before reading.

[0149] 2.4 Data Analysis

[0150] The obtained data are presented as mean and standard deviation of duplicate or triplicate and analyzed using analysis of variance (ANOVA). The difference between mean values ​​was evaluated using Tukey HSD comparison test (P < 0.05). All statistical analyses were performed using JMP Pro15 (SAS Institute, USA) and plotted using GraphPad Prism9 (GraphPad Software Inc., USA). Ternary graphs were drawn using MATLAB (R2022a, MathWorks, Natick, MA, USA).

[0151] 3. Results and Discussion

[0152] 3.1 Effects of biopolymer ratio, PS and concentration on the formation of ternary complexes

[0153] Figure 2The effects of different polysaccharide and biopolymer ratios on the ternary complex formation of LF and gelatin at pH 4 are shown. The charge density, structural characteristics and approximate molecular weight of the five polysaccharides are listed for reference (Table 1). In general, soybean soluble polysaccharide (SSP) and gum arabic (GA) are branched polysaccharides with a charge density below 0.3; while high methoxyl pectin (HMP), Kappa carrageenan (Kappa) and Iota carrageenan (Iota) are linear polysaccharides with charge densities of 0.3-0.6, 0.5 and 1, respectively. The total biopolymer concentration of each ternary system was the same (0.2 w / v%).

[0154] A ternary diagram was used to design the mixing ratio of the three biopolymers ( Figure 2 ); the scales of the three axes indicate the mass ratio of the biopolymer added to the ternary mixture. The darker the gray of the ternary mixture at certain biopolymer ratios, the higher the turbidity of the mixture (3-7), which further indicates stronger interactions and complex formation.

[0155] Table 1. Charge density, molecular weight and supplier of the five polysaccharides used in this study (molecular weight information was provided by the supplier).

[0156]

[0157]

[0158] * Charge density in mol / mol monosaccharide

[0159] As in Figure 2 As shown in , different PS systems exhibit different maximum turbidity (T max ); when turbidity greater than 2 is found, complex formation is indicated. The maximum turbidity represents the maximum degree of complexation in the system and the strength of electrostatic interaction, which is related to the relative amount of oppositely charged groups in each solution. In general, PS with branched chains / structures (GA and SSP) show smaller T values ​​than PS with linear structures (HMP, Kappa and Iota carrageenan). max The later systems also exhibited larger complex formation areas (when T > 3), presumably due to their larger negative charges and higher charge density. Considering the relatively low complex formation (0.2%) in the GA and SSP systems, an increased concentration (1%) was applied, e.g. Figure 3 shown.

[0160] For the GA-LF-G system, when the mixture consisted of 60-80% LF and 20-40% GA, a complex was formed ( Figure 2), while the concentration of gelatin seemed to have little effect. Overall, the SSP-LF-G mixtures showed very limited complex formation under all conditions studied and exhibited relatively low turbidity less than 3 over a range of mass ratios ( Figure 2 For the HMP-LF-G system, when the mixture consisted of 30-90% LF, 30-90% HMP and 40-50% gelatin, a complex was formed ( Figure 2 For Kappa-LF-G and Iota-LF-G mixtures, the complex formation range shifted to 50-90% LF, 50-90% Kappa or Iota, and less than 50% gelatin ( Figure 2 ). When linear polysaccharides are involved, higher gelatin concentrations (>50%) appear to be detrimental to complex formation, showing lower turbidity. While not wishing to be bound by any particular theory, the higher charge density and more negative charges carried by HMP, Kappa, and Iota compared to SSP and GA may contribute to the increased ability of these polysaccharides to form complexes with LF at the high mass ratio of LF (Tables 1 and 2).

[0161] Table 2. Zeta potential of biopolymers at different pH levels and concentrations (w / v%).

[0162]

[0163]

[0164] Considering the relatively low turbidity in the SSP and GA systems at a total concentration of 0.2 w / v%, the concentration increase (1 w / v%) of the biopolymers in these two ternary systems was further investigated ( Figure 3 ). Increased concentrations enhance the interaction and T max , especially in the GA ternary system. Although higher concentrations are expected to promote a higher degree of complexation (due to increased density of opposite charges in solution and decreased molecular distances), the degree of complexation is much greater than expected in the GA-LF-G system and is less pronounced than expected in the SSP-LF-G system. The zeta potentials (representing charge density) of GA and SSP are very similar at 0.2 w / v% or 1 w / v% concentrations (Table 2), so without wishing to be bound by any particular theory, differences in chain flexibility between GA and SSP may be responsible for the differences observed in their formation of complexes with LF and gelatin.

[0165] The ternary complex formed at pH 7 was also studied (data not shown). However, the samples under all biopolymer ratios all showed very low turbidity (<2), indicating that limited complex formation. Because LF and gelatin have limited positive charge at pH 7, the electrostatic interaction at all biopolymer ratios is low. Overall, the final selected concentration is 1% in GA and SSP ternary systems, and is 0.2% in HMP, Kappa and Iota ternary systems. When all biopolymers obtain relatively high charge, pH conditions are fixed to pH 4. According to these triangular turbidity diagrams, the biopolymer ratio with the highest turbidity is selected as the condition for forming complex, because they show higher complex formation levels in each system. Specifically, the selected biopolymer ratio is respectively GA-LF-G 2-6-2, SSP-LF-G 4-5-1, HMP-LF-G 4-5-1, Kappa-LF-G 3-6-1, Iota-LF-G2-6-2.

[0166] 3.2 Zeta potential and particle size of the ternary complex

[0167] As a proof of concept, the zeta potential of the ternary mixtures formed at pH 4 was selectively evaluated. In general, ternary mixtures with fixed gelatin and LF ratios were chosen to study the effect of the addition of PS or LF on the zeta potential of the ternary mixtures. Figure 4 As shown in , with the addition of negatively charged PS, the zeta potential of the ternary mixture gradually decreases from positive to zero, and then further decreases to negative. Most importantly, as Figure 2 and Figure 3 As shown, the ratio when the overall zeta potential is close to zero is also a condition for showing high turbidity. This is because, when the overall zeta potential reaches zero, it means that all biopolymers have similar opposite charges on the surface. They tend to form complexes due to electrostatic interactions, and the repulsive interactions between biopolymers decrease as the system has the least charge, thereby further promoting the formation of larger complexes. The particle size of the ternary mixture of GA and Iota under different ratios and pH conditions was also selectively measured and contrasted. As shown in Table 3, the mixture sample of GA-LF-G 2-6-2 showed large average particles when forming complexes, while at pH 7, the same ratio showed a small average size, indicating limited complex formation. Similarly, the sample of Iota-LF-G 2-6-2 showed a larger size than the result obtained in the GA-LF-G system, which may be due to the higher charge density of Iota, although the total concentration of the Iota system is lower than the total concentration in the GA system.

[0168] Table 3: Average particle size of PS(GA / Iota)-LF-G mixtures at various biopolymer ratios at pH 4.

[0169]

[0170] 3.3 Effect of salt on complex formation

[0171] Figure 5 The turbidity of the ternary complex formed at different salt concentrations (up to 500mM) at pH 4 and the ratio obtained from the above study are shown. Salt generally has a negative impact on ternary complex formation, especially at high concentrations (>100mM), because salt weakens or shields the electrostatic interactions between these polymers. An interesting finding is that the turbidity of the GA-LF-G ternary complex increases at low salt concentrations (0-50mM) and then gradually decreases with the increase in salt concentration. Generally, the ternary complex formed by SSP and HMP is more sensitive to salt, and the turbidity is close to zero when the salt concentration is higher than 100mM (which is also called the critical salt concentration). The complex formed by GA is less sensitive to salt, and the critical salt concentration is about 200mM. The complex formed by Kappa and Iota carrageenan is the least sensitive to salt, because they can maintain their turbidity greater than 1 even at a salt concentration of 500mM. Overall, most ternary complexes can be maintained at a salt concentration below 50mM, preferably below 30mM.

[0172] 3.4 Composite yield, composite efficiency and loading ratio of LF in ternary composites

[0173] After obtaining the required conditions for forming the ternary complex, the ternary mixture solution was centrifuged and the supernatant containing the uncomplexed biopolymer was removed. The resulting precipitate containing the composite biopolymer was then freeze dried. The average yield, composite efficiency and final mass loading ratio of LF in the freeze-dried composite were measured (Table 4). The ternary mixture formed by straight chain, high-charge PS Kappa and Iota carrageenan showed the highest composite yield (70-80%) and the highest composite efficiency (96%). On the contrary, the mixture formed by straight chain, less charged PS HMP provided a medium composite yield (about 40%) and a medium composite efficiency (52%). The ternary mixture formed by branched, even less charged PS, GA and SSP showed a lower yield (40% and 17%) and a medium to low composite efficiency (50% and 20%). The high complexation efficiency (96%) in the Kappa-LF-G and Iota-LF-G mixtures indicates that almost all of the LF present in the mixture was incorporated into the complex, while the GA / HMP-LF-G mixture incorporated only about 50% of the available LF. Overall, the results show that complexes formed from linear and highly charged PS, Kappa and Iota exhibited higher yields and complexation efficiencies than those formed with more neutral PS, HMP and GA. This result is consistent with the turbidity results, i.e., the highly charged polysaccharides, Kappa and Iota carrageenan exhibited higher turbidity and complex formation with LF and gelatin, indicating stronger interactions in these ternary complexes.

[0174] Table 4. Compounding efficiency (%), yield (%) and LF loading ratio (%) of ternary composites at the desired mixing ratio.

[0175]

[0176] The final mass ratio of LF in the freeze-dried complexes was quantified using three different methods: Bradford assay, bicinchoninic acid (BCA) assay, and HPLC. Based on these three methods, the mass ratio of LF in the complexes including GA, SSP, or HMP was in the range of 40-56% (w / w). Due to the interaction of the Bradford reagent with the sulfate groups of carrageenan, the Bradford assay underestimates the mass ratio of LF in the Kappa / Iota carrageenan ternary complex. Due to the strong negative charge of the sulfate groups of Kappa / Iota carrageenan, HPLC analysis is also limited to obtaining the LF peak from the Kappa / Iota carrageenan ternary complex. Therefore, the mass ratio of LF in the Kappa / Iota carrageenan ternary complex measured by the BCA method is more reliable, which is about 68-75% (w / w). The loading ratio of LF in GA complex was about 52%, that in HMP complex was about 40-42%, and that in Kappa and Iota carrageenan complex was about 54-68% (Table 4-). The relatively high mass ratio of LF in the carrageenan ternary complex can be expected because these two polysaccharides carry much higher negative charges to form complexes with LF through electrostatic interactions.

[0177] 3.5 Microscopy of the formed complexes

[0178] The ternary complexes were studied by optical microscopy under selected conditions (pH, concentration and ratio) and Figure 6 As shown. Interestingly, different complex structures are formed in those ternary systems. GA and SSP systems show spherical structures to some extent, while HMP, Kappa and Iota systems show irregular polymer network structures. The former complex shows the formation of aggregate complexes, while the latter shows the formation of interpolymer complexes. In general, aggregate and complex development follow the same initial path. Initially, soluble polymer intracomplexes are formed under specific pH, ratio and ionic strength, and then as the biopolymer ratio continues to approach the conditions when the total charge reaches zero, the soluble complexes begin to interact with each other to form interpolymer complexes, and then bulk phase separation occurs. Generally, aggregates are formed when PS or protein has a low charge density or a very flexible main chain (such as gelatin, acacia gum and gum arabic). And when the PS or protein in the system is highly charged and / or has a very hard linear structure (such as carrageenan, gellan gum or xanthan gum), interpolymer complexes, also known as coprecipitates, are formed. The formation of intrapolymer complexes can be related to the greater binding affinity between biopolymers, which results in strong interactions.

[0179] Figure 7Confocal microscopy of the SSP, GA, HMP, Kappa and Iota ternary system with FITC-labeled LF (light grey) is shown, and Fig.17 SEM images are shown in panels A1-E1 and A2-E2 of FIG. Interestingly, the GA-LF-G ternary complex appears as a multiphase aggregate droplet, which means that multiple aggregate droplets are located within a larger aggregate droplet. In addition, LF (marked in green by FTIC) appears to be located in the inner phase aggregate. SEM images of the GA-LF-G complex after vacuum drying overnight ( Fig.17 Panels A1 and A2 of Figure 1 show that the GA-LF-G complex becomes compressed flat particles due to water evaporation, indicating the liquid-like properties of the aggregates. In the confocal images, scattering of SSP-LF-G nanoscale aggregate particles can be seen, indicating a low yield (8%) of the formed SSP-LF-G complex, while the HMP-LF-G, Kappa-LF-G, and Iota-LF-G complexes all show characteristic morphologies associated with dense interpolymer network structures ( Figure 7 ). SEM images confirmed the interpolymer complex structure of the ternary complex using these three linear polysaccharides, HMP, Kappa and Iota ( Fig.17 Small Figures C1, C2; D1, D2; and E1, E2)

[0180] Although multiphase aggregate droplets have been reported recently in biological systems, to our knowledge, this is the first time that this phenomenon has been observed in food-grade biopolymers, particularly protein-polysaccharide systems. While not wishing to be bound by any particular theory, it is believed that the main driving force for the formation of aggregate complexes in multiphase droplets is the different critical salt concentrations and densities. The SSP-LF-G ternary complex appears as a conventional single-phase aggregate droplet. For the HMP and Iota ternary systems, the confocal microscopy images are similar to the optical microscopy images, indicating an inter-polymer complex structure of the ternary complex including linear polysaccharides.

[0181] 3.6 Thermal stability of LF in the ternary complex

[0182] 3.6.1 Optical images, turbidity and particle size of LF ternary composites after heat treatment

[0183] It is known that LF is easily denatured under heat treatment conditions at neutral pH. Therefore, in order to examine the thermal stability of LF in the complex samples, the freeze-dried complex samples were redispersed in 10 mM PBS buffer at pH 7 at 0.2% (m / v) and then heat-treated under pasteurization conditions (75°C / 2 minutes and 90°C / 2 minutes). Pure LF is easily denatured and aggregated in PBS buffer at pH 7. In addition, pure LF tends to aggregate to a higher degree at 90°C / 2 minutes than at 75°C / 2 minutes, with the former condition showing a more turbid solution. Compared with pure LF, the LF complex presented a clearer solution after heat treatment, regardless of the complex solution. From Figure 8 This can be observed more directly in the turbidity graphs of Figure 2, where pure LF shows a large increase in turbidity from <0.5 to >4 in PBS buffer after heating, while the turbidity increase of LF in the complex sample is very limited (<1). Fig. 9 The particle size variation of LF and the redispersed complex solution after heat treatment is shown. The aggregation of LF protein causes the significant increase of particle size from <100nm to >2000nm, while the complex solution only shows the slight variation of particle size. Kappa and Iota complexes even show the reduction of particle size, probably because heating promotes the dissolution of the complex formed by decomposing the large complex into smaller soluble complexes. As previously mentioned, the complex formed by Kappa and Iota carrageenan shows the strong interaction between LF and G, which enables them to form larger particles, and therefore shows lower solubility in solution. Although it is not desired to be bound by any particular theory, it is speculated that the heating process can induce the large ternary complex to decompose into smaller complex particles, thereby improving their solubility and reducing their overall particle size. However, they are still regarded as complexes, because their particle size is still larger than the particle size of natural LF (measured value is about 60nm).

[0184] 3.6.2 SDS-PAGE of LF and ternary complex after heat treatment

[0185] The SDS-PAGE of pure LF and LF in the ternary complex after heat treatment in PBS buffer was analyzed and Figure 10-11As shown. In pure native LF, a clear band is shown at about 75 kDa, which is the band where the LF protein is located. After heating at 75°C / 2 minutes and 90°C / 2 minutes, the density of the LF band becomes significantly lighter than that of the unheated LF due to thermal degradation. This result is consistent with the changes observed in the CD signal and the intrinsic fluorescence peak intensity of pure LF described below. In the complex sample, the density of the LF band also decreased, but the decrease was much smaller than that of pure LF. The GA-LF-G complex showed negligible changes in the LF band after heating treatment. Compared with the GA-LF-G complex, other PS ternary complexes showed slightly more LF degradation. For the Kappa and Iota complexes, the bands in SDA-PAGE showed obvious tailing; although not wishing to be bound by any particular theory, this is probably due to the stronger binding interaction between LF and the negative sulfate groups of carrageenan and the more rigid structure of the complex, which affects the separation of LF molecules in SDS-PAGE.

[0186] 3.6.3 Analysis of LF retention percentage in the ternary complex after heat treatment by HPLC

[0187] In order to mathematically quantify the amount or ratio of LF degraded or retained in the complex after heat treatment, an HPLC method for LF analysis was developed and applied. The ternary complexes of GA-LF-G, SSP-LF-G and HMP-LF-G were focused on before and after heat treatment because the strong binding interactions between LF and Kappa and Iota carrageenan would interfere with the method. The percentage of LF retention in pure LF at different concentrations was first analyzed. The percentage of LF retention in the ternary complex was measured and compared with the corresponding binary complex. As shown in Table 5, LF at a concentration of 0.05-0.2% (w / v) (i.e., 0.5-2 mg / mL) in PBS buffer (pH 7) retained only half of the LF after heating at 75°C / 2 minutes. After heating at 90°C / 2 minutes, almost all of the LF was denatured, with less than 10% of LF retained at all studied concentrations.

[0188] A comparison between LF ternary complexes and common binary complexes (LF with GA, SSP and HMP) was also performed. The binary complexes showed increased LF retention percentages of 70-80% and 50-60% after heating at 75°C / 2 minutes and 90°C / 2 minutes, respectively. Compared with the binary complexes, the ternary complexes showed enhanced LF stability during thermal treatment. The LF in the ternary complex was only slightly degraded after heating at 75°C / 2 minutes, with an 80-100% retention ratio. Even at 90°C / 2 minutes of heating, the retention ratio of LF was 70-99%, which was seven to nine times higher than the pure LF sample, and almost doubled compared to the binary complex. In the GA-LF-G ternary complex, LF was almost not degraded under both heating conditions, showing the highest LF thermal stability among all ternary complex samples. Although not wishing to be bound by any particular theory, the enhanced LF thermal stability in the ternary complex described herein can be attributed to additional complex interactions from additional biopolymers. In addition to the interaction between LF and PS, without being bound by any particular theory, the interaction between gelatin and PS may enhance the interpolymer interactions within the complex, thereby strengthening the protection around LF and limiting protein structural changes during heat treatment.

[0189] Table 5: LF retention percentage of heat-treated LF and binary / ternary complexes in PBS buffer (10 mM, pH 7) quantified by HPLC analysis.

[0190]

[0191] 3.6.4 Structural changes of LF in the ternary complex after heat treatment

[0192] The CD spectra of the LF ternary complex before and after heat treatment were also measured to investigate the secondary structural changes of LF during the heat treatment. Fig.12As shown, pure native LF has a positive peak at 196nm and a negative peak at 210nm, indicating the β and α structures of the LF protein. It is reported that LF consists of 16-20% α-helix, 33-42% β-strand, 10-12% β-turn and 30-34% disordered structure (Lin et al., 2022; Wang et al., 2017). After heating, pure LF showed a significant decrease in peak intensity at 210nm, indicating the loss of α-helix structure. The higher the heating temperature, the greater the decrease in peak intensity. Especially after heating at 90℃ / 2 minutes, the CD spectral signal and peak intensity of LF are very low, indicating a high degree of degradation of LF and the loss of α-helix. However, the CD spectra of all complex solutions hardly changed even after heating until 90℃ / 2 minutes, indicating that the LF secondary structure was well preserved in the complex solution during the heating process ( Fig.12 Specifically, the CD spectrum of the GA-LF-G complex solution showed little change after heat treatment, indicating a high degree of preservation of the native structure of LF ( Fig.12 Our previous work also found that the thermal stability of LF secondary structure was improved by complexing with negatively charged soluble soybean polysaccharides (Lin et al., 2022); however, such limited changes in LF secondary structure exhibited in the current GA-LF-G sample have not been reported before.

[0193] To further understand the structural changes of LF in the system after the heating process, the intrinsic fluorescence intensity of the unheated and heated samples was studied, as Fig.13 and 14 As shown. The fluorescence emission maximum peak of pure LF shows a red shift from 333 to 339 nm in the fluorescence spectrum, which is a typical feature of tryptophan residues in unfolded proteins, thus indicating the unfolding of LF during the heating process. In addition, the peak intensity of LF increased by 29% after heating, indicating that the quenching of tryptophan after LF unfolding during the heating process was reduced ( Fig.14 After heat treatment, the emission peak of the complex sample showed a smaller red shift, indicating less unfolding of the protein structure ( Fig.14 ). In addition to SSP, the increase in peak intensity of the composite samples after heating is also smaller than that in pure LF (4.8-18.7%) ( Fig.14 Overall, the intrinsic fluorescence results showed that LF in ternary complexes (especially GA, HMP, Kappa or Iota systems) retained more native protein structure and unfolded less after the heating process compared to pure LF.

[0194] Table 6. Quantitative analysis by HPLC of LF retention ratios of LF and LF ternary complex in PBS buffer (10 mM, pH 7) after heat treatment at 145°C for the indicated time periods.

[0195]

[0196]

[0197] Different superscript letters indicate statistically significant differences (P < 0.05) between means compared using Tukey-Kramer HSD.

[0198] Considering the common use of ultra-high temperature (UHT) treatment in industrial food processing, the thermal stability of LF heated at higher heating temperatures (about 145°C) for 0-60 seconds was studied (Table 6). HPLC analysis found that the LF solution began to show observable denaturation or loss of native LF after heating in an oil bath for 30 seconds, with a retention ratio of 16.5%, while only 7.8% was retained after heating for 60 seconds. The GA-LF-G ternary complex showed almost no change after heating at 145°C for 30 seconds, while the HMP-LF-G ternary complex had poor elasticity and remained intact only for 10 seconds. After 60 seconds of UHT treatment, both complexes showed a significant decrease in LF retention (84.1% for GA-LF-G and 80.0% for HMP-LF-G). The turbidity and particle size changes of the LF and ternary complex solutions were also analyzed, showing results consistent with the LF retention analysis ( Fig.18 Specifically, the LF solution showed turbidity after being treated at 145°C for 30 seconds ( Fig.18 Panel A) and average particle size ( Fig.18 (B), while the ternary composite showed negligible changes in turbidity and particle size after treatment at 145 °C for 60 s. The ternary composite maintained the stability of LF even under high temperature conditions.

[0199] 3.7 Antimicrobial properties of LF in ternary composites before and after heat treatment

[0200] LF is known to exhibit antibacterial capabilities against both Gram-positive and Gram-negative bacteria and it is desirable to retain these properties while increasing thermal stability. The mechanism of LF's antibacterial activity is not well understood at present. The antimicrobial properties of LF were evaluated in pure LF and composited LF samples before and after heat treatment. The aim of this part of the study was to examine whether composites would affect the functionality of LF and whether it could retain this capability after heat treatment. Antimicrobial capability was chosen as a representative biological functionality of LF because it can be performed easily and relatively safely in most biological laboratories.

[0201] Considering that Staphylococcus aureus is one of the most common pathogens in dairy products, it was selected as the target Gram-positive bacteria. The MIC (minimum inhibitory concentration) study of LF against S. aureus was first conducted, which was defined as the lowest concentration of LF that could inhibit the growth of bacteria by half compared with the control group ( et al., 2020). Fig.15 As shown in panel A, the MIC of LF against S. aureus is 0.1%, because the OD625 nm value in 0.1% LF is only half of that in the control sample, which means that 0.1% LF is sufficient to inhibit 50% bacterial growth. In the redispersed ternary complex solution (0.2% w / v), the concentration of LF is about 0.1-0.14%, so it is suitable for antibacterial tests. Fig.15 Panels BD show the OD625nm values ​​of the unheated samples or the OD625nm values ​​of the samples heated after 75°C / 2 minutes or 90°C / 2 minutes. Pure polysaccharides and gelatin did not show any antibacterial effect and even promoted bacterial growth (data not shown) because they can be consumed by bacteria as an energy source. Our initial ternary complex showed an OD625 similar to that of native LF, confirming that the LF functionality was well preserved after the ternary complex was formed before heat treatment of LF.

[0202] For unheated samples ( Fig.15 (B), LF showed obvious antibacterial activity after 24 hours of incubation, with the OD625nm value being half that of the control group. The ternary complex sample also showed an inhibitory effect; however, its effect was less than that of pure LF. Although not wishing to be bound by any particular theory, this may be because LF is complexed / encapsulated in the ternary complex, which may affect the interaction between LF and bacteria and further affect the inhibitory effect to some extent.

[0203] After heat treatment at 75°C / 2 minutes ( Fig.15 In panel C), pure LF lost its inhibitory effect on bacteria and even promoted bacterial growth, probably because the bacteria could use the degraded LF fragments as an energy source. However, the heat-treated ternary complex showed a significant inhibitory effect, with the OD625nm value being about half that of the control group. This effect lasted until 48 hours of incubation. Fig.15 As shown, the resulting heat-treated ternary complex exhibited enhanced antibacterial effects. While not wishing to be bound by any particular theory, the improved antibacterial effects after heat treatment at 75°C can be attributed to the degradation of the ternary complex structure and the partial exposure or release of LF during the heating process, which promotes the interaction between LF and bacteria ( Fig.15 Figure C).

[0204] Nevertheless, partial denaturation of LF at 90 °C resulted in a significant decrease in the antibacterial activity of the ternary complex ( Fig.15 The formed ternary complex seems to exhibit a temperature-responsive release of LF. During the heat treatment, LF can be gradually released from the complex and still maintain its native structure and antibacterial ability. In the sample heat-treated at 90℃ / 2min ( Fig.15 In panel D), the loss of inhibitory effect of LF and the presence of bacterial growth are more obvious, as it shows even higher OD625nm values ​​compared to the counterpart treated at 75°C / 2 minutes. However, the ternary complex still showed about 50% inhibition of bacterial growth, with OD 625nm values ​​half of those of the control sample, especially in the ternary complexes of GA, SSP and HMP. The ternary complexes formed by Kappa and Iota carrageenan showed lower antibacterial capacity (i.e., higher OD values) compared to the other three PS, probably due to their strong binding to LF, thereby limiting the release of LF to exert antibacterial effects. Overall, the results show that pure LF has a significantly reduced antibacterial capacity after heating, while the antibacterial capacity is well maintained in the tested ternary complexes.

[0205] E. coli is a common spoilage Gram-negative bacterium in food products, so the antibacterial activity of LF and our ternary complex against E. coli was also tested. During the 24-hour incubation period, the OD625 of E. coli in the control sample was slightly higher than that of S. aureus, indicating that the bacterial growth rate of E. coli is generally faster than that of S. aureus ( Fig.15 Small Figure A and Fig.16 (panel A). Although the MIC of LF against E. coli was similar to that of LF against S. aureus, which was about 0.1 w / v%, the antibacterial effect of LF against E. coli was weaker than that against S. aureus, as the E. coli samples all showed higher OD625 values ​​after 24 h of incubation. The higher environmental resistance of Gram-negative bacteria than Gram-positive bacteria is due to the protective, impenetrable cell wall of Gram-negative bacteria surrounded by an outer membrane, which Gram-positive bacteria lack (Breijyeh et al., 2020). For the unheated samples, LF and the LF ternary complex showed antibacterial effects against E. coli within 24 h of incubation ( Fig.16 Similar to the results against S. aureus, the heated LF samples lost their antibacterial effect against E. coli after heat treatment, which is due to the thermal denaturation of LF ( Fig.16 C and D), while the ternary complex retained the antibacterial effect, showing an OD625 value significantly lower than that of the control group.

[0206] In general, the conditions (ratio, pH and concentration) for the formation of ternary complexes of LF, gelatin and different polysaccharides were identified for each ternary system based on the turbidity diagrams. Branched, less charged gum arabic and SSP formed coacervate complexes with LF and gelatin at a total concentration of 1%. Considering the relatively high solubility and low viscosity of GA and SSP, further higher concentrations may also be applicable in both systems. Straight-chain, highly charged HMP, Kappa and Iota formed interpolymer complexes with LF and gelatin at a total concentration of 0.2%. Appropriate hardening and / or cross-linking procedures can increase the yield of the formed complexes. Further freeze-drying and / or spray-drying processes can make the coacervate complexes into microcapsules. Based on HPLC analysis and CD spectroscopy, the formed complex samples were confirmed to retain most of the native LF structure even after heating to 90°C / 2 minutes. Furthermore, the ternary complexes including GA, SSP or HMP were confirmed to maintain the antimicrobial ability of LF (e.g., capable of inhibiting bacterial growth by about half compared to the control group, as shown by OD625nm value) after pasteurization conditions (75°C / 2 min and 90°C / 2 min) under neutral pH conditions.

[0207] Example 2

[0208] In this study, we fabricated a thermostable lactoferrin (LF) ternary complex via electrostatic interactions under laboratory-scale and industrial-scale processes.

[0209] The formed LF complex exhibited improved thermal stability compared to single LF under high temperature short time (HTST) / ultra high temperature (UHT) treatment in different matrices including water, skim milk and acid whey beverage. The retention ratio of LF after heat treatment was quantified by HPLC and ELISA analysis, and the protein secondary structure was further confirmed by circular dichroism spectroscopy. The biological activities of LF, including antibacterial (Escherichia coli and Staphylococcus aureus) and antiviral (coronavirus) activities, were well retained in the complex after heat treatment.

[0210] During storage, the LF complex ingredients showed good solubility, LF retention ratio and bioactivity after storage for 12 months at 25°C. The LF complexes formed in different food models (water, skim milk and acid whey beverage) showed stable physicochemical properties (e.g., turbidity and particle size) under storage conditions of 4°C for 12 months and 25°C for 6 months, and produced minimal undesirable organoleptic properties.

[0211] The foregoing is illustrative of the present invention and is not to be construed as limiting thereof. The present invention is defined by the following claims, with equivalents of the claims to be included therein.

Claims

1. A composite comprising: protein; anionic biopolymers; and Cationic biopolymers; The protein, anionic biopolymer and cationic biopolymer are bound together by electrostatic interactions.

2. The complex of claim 1, wherein the complex has a zeta potential of about -5 mV to about +5 mV, optionally wherein the complex has a net negative charge at a pH of about 6.5 to about 7.

5.

3. The complex of claim 1 or 2, wherein the complex comprises protein in an amount of about 30% to about 85% w / w, a cationic biopolymer in an amount of about 5% to about 40% w / w, and an anionic biopolymer in an amount of about 5% to about 40% w / w, optionally wherein the complex comprises protein in an amount of about 40% to about 75% w / w, a cationic biopolymer in an amount of about 10% to about 30% w / w, and an anionic biopolymer in an amount of about 10% to about 30% w / w.

4. The complex of any preceding claim, wherein the protein has a net positive charge at a pH of about 3, 3.5 or 4 to about 4.5, 5, 6, 7 or 8, optionally wherein the protein has a zeta potential of greater than about +10 mV to about +30 mV at a pH of about 3, 3.5 or 4 to about 4.5 or 5.

5. A complex as claimed in any preceding claim, wherein the protein has a globular structure and / or is a milk protein.

6. The complex of any preceding claim, wherein the protein is soluble in water at a pH of less than about 8.

7. The complex of any preceding claim, wherein the protein is lactoferrin, alpha lactalbumin, lysozyme and / or osteopontin, optionally wherein the amino acid sequence of the protein has at least 70%, 75%, 80%, 85%, 90%, 95%, 96%, 97%, 98%, 99% or more sequence identity to one or more of SEQ ID NOs: 1-5.

8. The complex of any preceding claim, wherein the cationic biopolymer has a net positive charge at a pH of about 3, 3.5 or 4 to about 4.5 or 5, optionally wherein the cationic biopolymer has a zeta potential of greater than +10 mV to about +30 mV at a pH of about 3, 3.5 or 4 to about 4.5 or 5.

9. The complex of any preceding claim, wherein the cationic biopolymer has a pi and / or pKa of about 7 or more.

10. The complex of any preceding claim, wherein the cationic biopolymer is selected from gelatin, chitosan, lysozyme and / or polyamino acids, optionally wherein the cationic biopolymer is gelatin.

11. The complex of any preceding claim, wherein the anionic biopolymer has a net negative charge at a pH of about 3, 3.5 or 4 to about 4.5 or 5, optionally wherein the anionic biopolymer has a zeta potential of less than -10 mV to about -50 mV at a pH of about 3, 3.5 or 4 to about 4.5 or 5.

12. The complex of any preceding claim, wherein the anionic biopolymer has a zeta potential in the range of about -10 mV to about -55 mV at a pH of about 3, 3.5 or 4 to about 4.5 or 5, optionally wherein the anionic biopolymer has a zeta potential in the range of about -10 mV to about -25 mV or about -35 mV to about -55 mV at a pH of about 3, 3.5 or 4 to about 4.5 or 5.

13. The complex of any preceding claim, wherein the anionic biopolymer is a polysaccharide or a glycosaminoglycan, optionally wherein the anionic biopolymer is a branched polysaccharide or a linear polysaccharide.

14. A complex according to any preceding claim, wherein the anionic biopolymer is selected from gum arabic, high methyl pectin (HMP) (optionally HMP having a degree of esterification greater than 50%), Kappa-carrageenan, Iota-carrageenan, dextran sulfate, sodium hyaluronate, acacia gum, xanthan gum, gellan gum and / or a plant soluble polysaccharide (e.g., soy soluble polysaccharide and / or lupin soluble polysaccharide), optionally wherein the anionic biopolymer is gum arabic, acacia gum, dextran sulfate, sodium hyaluronate and / or a plant soluble polysaccharide, or the anionic biopolymer is HMP, Kappa-carrageenan, Iota-carrageenan, xanthan gum and / or gellan gum.

15. The complex of any preceding claim, wherein the anionic biopolymer has a pKa of about 4 or less.

16. A complex as claimed in any preceding claim, wherein the protein, cationic biopolymer and anionic biopolymer are each food-grade components, optionally wherein one or more of the protein, cationic biopolymer and anionic biopolymer are obtained and / or derived from natural products (e.g., foods, plants, animal by-products (e.g., milk), etc.).

17. The complex of any preceding claim, wherein the protein is lactoferrin, the anionic biopolymer is a polysaccharide, and the cationic biopolymer is gelatin, optionally wherein the anionic biopolymer is gum arabic.

18. The composite of any preceding claim, wherein the composite is a composite agglomerate in a liquid, optionally wherein the composite is a multiphase agglomerate in a liquid.

19. A complex as claimed in any preceding claim, wherein the complex has an aggregate-in-aggregate structure in a liquid and comprises an endoaggregate and an exoaggregate, optionally wherein the endoaggregate comprises the protein and the anionic biopolymer, and the exoaggregate comprises the anionic biopolymer and the cationic biopolymer.

20. The complex of any preceding claim, wherein the complex is an inter-polymer complex.

21. The complex of any preceding claim, wherein the protein has increased stability (e.g., reduced protein degradation) after exposure to a temperature of about 70°C to about 80°C, 90°C, or 100°C for about 1 minute to about 60 minutes compared to the stability of the protein alone (i.e., not present in the complex) after exposure to the same temperature for the same period of time.

22. The complex of any preceding claim, wherein the protein degrades by less than about 30% as measured by high performance liquid chromatography after exposure to a temperature of about 70°C to about 80°C, 90°C, or 100°C for about 1 minute to about 60 minutes.

23. The complex of any preceding claim, wherein the activity of the protein is increased compared to the activity of the protein alone after each is stored under the same conditions (e.g., storage in a dry composition at about 20°C to about 30°C for about 1, 2, 3, 4, 5 or 6 months).

24. The complex of any preceding claim, wherein the solubility of the complex in a composition (e.g., water, a buffer, milk (e.g., skim milk) and / or an acid whey beverage) remains within about 30% of its original solubility prior to storage and / or exposure after storage in a closed container at about 4°C to about 25°C for about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12 months and / or exposure to a temperature in the range of about 70°C or 75°C to about 80°C, 85°C or 90°C for about 30 seconds to about 2 minutes or exposure to a temperature in the range of about 100°C, 105°C, 110°C, 115°C or 120°C to about 125°C, 130°C, 135°C, 140°C or 145°C for about 2, 5, 10, 20 or 30 seconds to about 40, 50 or 60 seconds.

25. The complex of any preceding claim, wherein the amount of the biopolymer (e.g., the protein, the cationic biopolymer and / or the anionic biopolymer) present in the complex remains within about 30% of the amount of the biopolymer present in the complex prior to storage and / or the exposure after storage in a closed container at about 4°C to about 25°C for about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12 months and / or exposure to a temperature in the range of about 70°C or 75°C to about 80°C, 85°C or 90°C for about 30 seconds to about 2 minutes or exposure to a temperature in the range of about 100°C, 105°C, 110°C, 115°C or 120°C to about 125°C, 130°C, 135°C, 140°C or 145°C for about 2, 5, 10, 20 or 30 seconds to about 40, 50 or 60 seconds.

26. The complex of any preceding claim, wherein the antimicrobial capacity and / or activity (e.g., antibacterial activity against Gram-positive and / or Gram-negative bacteria and / or antiviral activity) of the biopolymers (e.g., the protein, the cationic biopolymer and / or the anionic biopolymer) present in the complex is maintained at about 4°C to about 25°C for about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12 months in a sealed container and / or exposed to about 70°C. or 75°C to about 80°C, 85°C or 90°C for about 30 seconds to about 2 minutes, or a temperature in the range of about 100°C, 105°C, 110°C, 115°C or 120°C to about 125°C, 130°C, 135°C, 140°C or 145°C for about 2, 5, 10, 20 or 30 seconds to about 40, 50 or 60 seconds, compared to the antimicrobial capacity and / or activity of the biopolymer prior to storage and / or said exposure.

27. The complex of any preceding claim, wherein the bioavailability of each of the proteins following ingestion by a subject is increased compared to the bioavailability of the protein alone.

28. The complex of any preceding claim, wherein the complex is a particle and the anionic and / or cationic biopolymer encapsulates the protein, optionally wherein the particle is a nanoparticle or a microparticle.

29. The complex of any preceding claim, wherein the complex in the liquid composition has an average size (e.g., diameter) of about 50 or 100 nm to about 150, 200, 300, 400, 500, 600, 700, 800, 900, 1000, 2000, 3000, 4000, 5000, or 6000 nm.

30. The composite of any preceding claim, wherein: The size (e.g., diameter) of the complex remains within ± about 20% of its original size after storage in a closed container at about 4°C to about 25°C for about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11 or 12 months and / or exposure to a temperature in the range of about 70°C or 75°C to about 80°C, 85°C or 90°C for about 30 seconds to about 2 minutes or exposure to a temperature in the range of about 100°C, 105°C, 110°C, 115°C or 120°C to about 125°C, 130°C, 135°C, 140°C or 145°C for about 2, 5, 10, 20 or 30 seconds to about 40, 50 or 60 seconds.

31. A complex as described in any of the preceding claims, wherein the protein degrades by less than 30%, optionally by less than 20%, as measured by high performance liquid chromatography after exposure to a temperature of about 145°C for about 2 seconds to about 60 seconds (e.g., high temperature short time (HTST) or ultra high temperature (UHT) treatment at about 145°C for about 2 seconds to about 60 seconds).

32. A complex as described in any preceding claim, wherein the antimicrobial capacity and / or activity (e.g., the antibacterial capacity and / or activity of the protein against Gram-positive and / or Gram-negative bacteria, and / or the activity) of the protein after exposure to a temperature of about 70°C to about 80°C or 90°C for about 30 seconds to about 2 minutes is retained and / or improved (e.g., increased) compared to the antimicrobial capacity and / or activity (e.g., the antibacterial capacity and / or activity of the protein against Gram-positive and / or Gram-negative bacteria, and / or the activity) of the protein alone, optionally after the same exposure conditions (e.g., the same temperature and temperature exposure time).

33. A composition comprising the complex of any one of claims 1-32, optionally wherein the composition is an aqueous composition.

34. The composition of claim 33, wherein the composition is a suspension.

35. A method for preparing a composite, the method comprising: providing a composition comprising a protein, an anionic biopolymer, and a cationic biopolymer at a pH in the range of about 3, 3.5, or 4 to about 4.5 or 5; and The composition is mixed to provide the composite.

36. The method of claim 35, wherein the protein, anionic biopolymer, and cationic biopolymer are each independently present in the composition in an amount of about 0.01%, 0.1%, 0.5%, 1%, 2%, 3%, 4% or 5% to about 6%, 7%, 8%, 9% or 10% by weight of the composition, optionally wherein the protein, anionic biopolymer, and cationic biopolymer are each independently present in the composition in an amount of about 0.01%, 0.1%, 0.5% or 1% to about 2% or 3%.

37. The method of claim 35 or 36, wherein the composition comprises an anionic biopolymer and a protein in a weight ratio of about 0.5:1 to about 1:5 (anionic biopolymer:protein), and / or wherein the composition comprises a protein and a cationic biopolymer in a weight ratio of about 1:1 to about 10:1 (protein:cationic biopolymer).

38. The method of any one of claims 35-37, wherein the composition comprises anionic biopolymer, protein, and cationic biopolymer in a weight ratio of about 1:3:1, about 4:5:1, or about 3:6:1 (anionic biopolymer:protein:cationic biopolymer).

39. The method of any one of claims 35-38, wherein mixing the composition is performed for about 15 minutes to about 60 minutes, optionally at a temperature of about 20°C to about 60°C.

40. The method of any one of claims 35-39, wherein providing the composition comprises forming an intermediate composition comprising the protein and the anionic biopolymer and adding the cationic biopolymer to the intermediate composition to provide the composition, optionally wherein the method further comprises mixing the intermediate composition at a temperature of about 20°C to about 60°C for about 15 minutes to about 60 minutes.

41. The method of any one of claims 35-40, further comprising hardening the composite, optionally wherein hardening the composite comprises adjusting the temperature of the composition to about 5°C to about 10°C and exposing the composition to a temperature of about 5°C to about 10°C for about 1 hour to about 6 hours.

42. The method of any one of claims 35-41, further comprising isolating the complex from the composition, optionally wherein isolating the complex from the composition comprises centrifuging, drying, freeze drying and / or spray drying the composition.

43. The method of any one of claims 35-42, wherein the total concentration of protein, anionic biopolymer, and cationic biopolymer in the composition is about 10% or less by weight of the composition, optionally about 5% or less by weight of the composition.

44. An article comprising the composite of any one of claims 1-32, the composition of any one of claims 33-34, and / or a composite prepared according to the method of any one of claims 35-43.

45. The article of claim 44, wherein the article is a food product (e.g., infant formula, dairy product, etc.), a nutritional supplement, a therapeutic drink, and / or a cosmetic.